Closure of the Eastern Paleo-Asian Ocean: Deformation and geodynamics - Qi’ang Fang; Yongjiang Liu; Qingbin Guan; Zhaoxu Chen; Boran Liu; Sanzhong Li (Gondwana Research, 2026)

Three-dimensional settling map for intelligent detection of activated sludge (AS) properties and health evaluation of AS based wastewater treatment - Jie Lei; Zhe Liu; Guoning Huang; Jiaxuan Wang; Rushuo Yang; Ying Du; Tianyu Han; Zhuangzhuang Yang; Ang Li; Yongjun Liu; Zhenmin Luo; Rong Chen (Water Research, 2026)

City landscape in sight: A crowdsourced framework for unlocking urban-scale window view perceptions from real estate imagery - Chucai Peng; Sijie Yang; Ang Liu; Yang Xiang; Zhixiang Zhou; Filip Biljecki (Landscape and Urban Planning, 2026)

Synergistic surface engineering enables high-efficiency and stable operation of low-bromine wide-bandgap perovskite solar cells - Zhenzhen Peng; Zhimin Fang; Yi Zhang; Rongyao Lv; Yu-Ang Liu; Dehan Li; Bairu Li; Luozheng Zhang; Shuang Chen; Shangfeng Yang; Jianning Ding (Chemical Engineering Journal, 2026)

Mechanistic characterization of the discrepancies in enrichment of nitrate between agricultural and urban-industrial rivers in the semi-arid areas of northern China: Insights from multi-element stable isotope analysis - Ang Dong; Yu Liu; Guiqi Liu; Guangzhi Rong; Shuaihao Liu; Mingjun Mo; Haixia Wang; Guoguang Wang (Journal of Hydrology, 2026)

Synergistic TP/APTES coating on PBT membrane enables superhydrophilicity and efficient oil-water separation - Shuiling Hong; Chenyang Li; Xin Wu; Ang Gao; Haoming Duan; Man Liu; Sijia Zhang; Shuo Yang; Leixin Yang; Dengkun Shu; Jingwei Xie; Bowen Cheng (Journal of Environmental Chemical Engineering, 2026)

Development of a global integrated environmental quality index for population health research - Wenjie Ruan; Qi Zhao; Xiaoyue Liu; Lina Ang; Haitong Zhe Sun; Wei Jie Seow (Environmental Pollution, 2026)

Structurally decoupled strongly hydrophobic biocathode enables high-performance flexible enzymatic biofuel cells for self-powered sensing - Jie Gao; Ang Xu; Jia Wu; Jinlong He; Ping Wang; Ying Liu; Qiang Wang; Bo Xu; Yuanyuan Yu; Man Zhou (Chemical Engineering Journal, 2026)

Enhancing power-to-hydrogen efficiency: A streamline-shaped flow channel design for alkaline water electrolyzers verified using a microfluidic experimental platform - Xiudong Duan; Ziyu Liu; Ang Lu; Jiachang Wan; Fan Chen; Desheng Li; Xiaomeng Ai; Chaolong Song; Jiakun Fang (Chemical Engineering Journal, 2026)

Topology-engineered hydrogel with cellulose nanosheets for robust and high-capacity zinc-ion batteries - Wenxuan Lei; Heng Huang; Wenyu Liu; Lingfeng Zhou; Guoping Li; Pan Chen; Zu Chang; Jiangfeng Qian; Ang Lu (Carbohydrate Polymers, 2026)

Mitigation of biogenic acidification via increased total alkalinity in high stocking density culture waters of Strongylocentrotus intermedius: Effects on growth and metabolism - Jiamin Li; Jiaqi Li; Minghui Jiao; Yadong Wang; Ang Li; Suyan Xue; Lulei Liu; Yuze Mao (Aquaculture, 2026)

Hydrodynamic interference and load evolution of staggered cylinder pairs under dam-break waves: An active learning-based Kriging modeling framework - Zhengjie Wu; Ang Liu; Yong Xu; Zexing Jiang; Bingling Wang; Yuanmin Zhao; Guoji Xu (Ocean Engineering, 2026)

Agricultural practices reshape molecular fingerprints of dissolved organic matter in aquatic ecosystems: A case study in China's Dai Village - Yifan Cui; Jinfu Liu; Shuailong Wen; Shaojuan Du; Kyoung-Soon Jang; Ang Hu; Jianjun Wang (Journal of Environmental Management, 2026)

Hypoxia-induced downregulation of cAMP drives Ganoderic acid biosynthesis and restricts biofilm development in Ganoderma lucidum - Siyi Wang; Li Tian; Faqin Li; Qin Wang; Yanan Tan; Yanda Ning; Xuewei Cao; Yueqian Liu; Jiaolei Shangguan; Huihui Li; Ailiang Jiang; Mingwen Zhao; et al. (Food Research International, 2026)

Activating lattice oxygen in Ni-doped SnO2 to break surface confinement for high-performance hydrogen sensing - Meili Wu; Yanbai Shen; Sikai Zhao; Ang Li; Jinzhou Bai; Qiang Zhao; Wenbao Liu; Zhenyu Yuan; Fanli Meng (Chemical Engineering Journal, 2026)

Tissue-specific energy trade-off strategies in Mytilus coruscus under combined stress of nano-TiO2 and marine heatwaves - Bing Liu; Sijie Fan; Menghong Hu; Li'ang Li; Mojiang Zhang; Xinyue Li; Moslem Sharifinia; Piotr Maszczyk; Nisha Singh; Waiho Khor; Hanafiah Fazhan; Wei Liu; et al. (Aquatic Toxicology, 2026)

Astronomically forced climate change during the Middle Oligocene-Early Miocene in the Pearl River Mouth Basin, Northern South China Sea - Shizhen Jia; Yanzhen Li; Mengqing Shang; Rui Liu; Linzhen Hu; Yongming Zhang; Xiuju Xing; Zi’ang Yang (Marine Geophysical Research, 2026)

METTL18-catalyzed histidine methylation of YTHDF2 promotes mRNA stability - Wen-Lan Yang; Meng-Xia Liu; Yue Han; Xing-Xing Li; Ye Gu; Xinyuan Tian; Mengqian Mu; Xiaolin Zhang; Yanzhe Wang; Xinyu Li; Yu-Sheng Chen; Chun-Chun Gao; et al. (Science China Life Sciences, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

The transformation and regeneration of the function of mianzi order in rural Chinese society: A conceptual framework based on relational dimension theory - Wenxiu Wang; Ang Liu (Journal of Rural Studies, 2026)

A sensory-calibrated electronic nose method for odor intensity quantification and grade identification in refrigerators - Shiwen Cheng; Li’ang Yin; Xiao Ye; Xiaozheng Liu; Yumei Qin; Yaqing Song; Suyun Zhang; Tengfei Yu; Chonghui Zhang; Shiyi Tian (Food Research International, 2026)

Research progress of cereals and their fermentation products in the prevention of metabolic dysfunction-associated steatotic liver disease - Chan Zhang; Yike Zhai; Arzugul Ablimit; Wenbo Liu; Duchen Zhai; Qing Sun; Lichao Dong; Chenran Yuchi; Ang Huang; Bobo Zhang; Chengjian Liu; Baoguo Sun; et al. (Food Bioscience, 2026)

Oral administration of dopamine boosts anti-Vibrio immunity in shrimp through Dorsal pathway activation - Zi-ang Wang; Shun Liu; Zexu Zhao; Xiaojia Liao; Linwei Yang; Hongliang Zuo; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2026)

A mimetic drug delivery system using graphene oxide as a component carrier in denitrification: Enhancing long-term stable carbon release and electron transfer capacity of carbon source materials - Ziyi Wang; Yawen Wang; Zhiqiang Chen; Jia Meng; Zhihao Gan; Peng Liu; Ang Li (Chemical Engineering Journal, 2026)

Predicting drug release from polymeric long-acting injectables using a machine learning approach to decode formulation-performance relationships - Tianqi Wang; Tianyu Liu; Xiaoying Xu; Joyce Wen Hui Ang; Somabha Mukherjee; Tina T. Wong; Jiong-Wei Wang; Matthias G. Wacker (Drug Delivery and Translational Research, 2026)

Multiscale Characterization of Anhydrous/Hydrous ScCO2 Effects on Coal: Time-Resolved Mineral-Pore Evolution and Divergent Control Mechanisms - Peng Liu; Wanjun Chen; Jingtao Yang; Baisheng Nie; Hengyi He; Hao Xu; Ang Liu (Gas Science and Engineering, 2026)

Cajaninstilbene acid induced apoptosis and cell cycle arrest in glioblastoma multiforme through mitochondrial ROS–mediated MAPK pathways - Yong-Ang Li; Tian-Zeng Bian; Hong Li; Jia-Wen Li; Liu-Tao Ma; Hao-Di Wu; Shuai Chen; Jia-Yi Chen; Hao Zeng; You-Bing Mao; Peng Wang; Qi Qiao (Food and Chemical Toxicology, 2026)

Designing hard-soft carbon composite anodes via a normalized pore volume-mass matching strategy for high-performance sodium storage - Xiaoqi Yu; Xiaoyu Xu; Hanyu Wei; Xiaofeng Zhang; Haiyan Liu; Chengwei Fan; Ang Li; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

A Physics-Data Co-Driven Approach for Blast-Induced Flyrock Control - Ang Li; Ningning Wang; Yaosheng Liu; Danial Jahed Armaghani; Biao He (Natural Resources Research, 2026)

Quantitative analysis of the mechanical behavior of granular sands subjected to particle pre-crushing - Wenli Lin; Guixu Li; Zhening Guo; Ting Yao; Ang Liu; Jiren Xie (Transportation Geotechnics, 2026)

Robust gut microbiota as a key protective barrier for Ruditapes philippinarum survival following an extreme-rainfall disturbance - Longzhen Liu; Lulei Liu; Ang Li; Zirong Liu; Suyan Xue; Jiaqi Li; Yuze Mao (Marine Environmental Research, 2026)

Enhanced treatment of high-algae water and membrane fouling mitigation by SPDA@MIL-101-modified polyethersulfone ultrafiltration membranes with magnetic field regulation and magnetic flocculant assistance - Meng Yao; Ang Li; Zhilin Ran; Xiaoqing Dong; Ruiyan Xiang; Ting Chen; Gang Liu (Journal of Environmental Chemical Engineering, 2026)

Tailored self-assembled molecule for efficient charge extraction and enhanced crystallization in wide-bandgap perovskite solar cells - Haojun Hu; Xianglang Sun; Xuke Yang; Zongbao Li; Peiyan Zhang; Xinyu Yu; Shi'ang Li; Zifan Lin; Dayu Liu; Ziyang He; Chuyun Deng; Longhui Zeng; et al. (Chemical Engineering Journal, 2026)

Competitive adsorption performance of volatile organic compounds on ZSM-5: Key influence factors and mechanisms - Yanling Zhao; Huan Liu; Ang Gao; Zhong Ji; Haoyue Zhang; Hao Huang; Lejin Xu; Hong Yao (Chemical Engineering Journal, 2026)

Carrier-free nanoparticles derived from Huanglian Jiedu decoction target ATP5F1C to eliminate senescent cells and ameliorate pulmonary fibrosis - Ying Zhang; Lirun Zhou; Yajian Li; Weiling Wang; Tong Yang; Qianyu Zhang; Hechen Tang; Jiayun Guo; Ling Huang; Chen Wang; Zheng Chu; Ang Ma; et al. (Chemical Engineering Journal, 2026)

Serum Endogenous Opioid Levels are Associated with Self-Injury Severity in Adolescents with Non-Suicidal Self-Injury and Comorbid Depression - Jin-Jun Ding; Xiao-Li Liu; Ang Li; Yi-Yao Liang; Yu-Bo Wang; Xiao-Na Zhu; Jie Li; Jie Weng; Lan Yan; Wen-Wen Duan; Zi-Chen Zhang; Ti-Fei Yuan; et al. (Neuroscience Bulletin, 2026)

Microbial metabolism regulates the stabilization of rhizodeposition-derived carbon in soil aggregates and mineral fractions under long-term tillage - Wen-Sheng Liu; Ben-Shun Liu; Zi-Ang Wang; Yong-Qiang Xu; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2026)

Accessibility dynamics with high-speed railway network expansion: A line-specific, granular analysis - Mengying Cui; Lijie Yu; Zhe Dai; Ang Ji; Keyue Liu; David Levinson (Travel Behaviour and Society, 2026)

Thiophene-based styrene derivative improves colitis symptoms in DSS-induced BALB/C mice through AhR-mediated gut barrier function and inflammatory responses - Ang-Kun Yang; Yong-Liang Li; Yan-Ying Chen; Yan Liu; Zhi-Yun Du; Chang-Zhi Dong; Bernard Meunier; Hui-Xiong Chen (Toxicology and Applied Pharmacology, 2026)

The dual nature of neuroticism: distinct dimensions impact longevity and well-being - Yini He; Jing Xiao; Ke Hu; Tian Gao; Yan Yan; Yu Yu; Lei Wang; Kaixin Li; Wenkun Lei; Kun Zhao; Changsheng Dong; Xiaohan Tian; et al. (Science Bulletin, 2026)

Contrasting responses to environmental stresses for macroinvertebrates and benthic algae in subtropic Qinhuai rivers - Lei Han; Ming Chen; Song Bai; Ang Hu; Peixuan Zhang; Beryl Ochieng; Yifan Cui; Jinfu Liu; Shaojuan Du; Hao Wu; Xiefa Song; Kang Song; et al. (Journal of Hydrology, 2026)

Sustainability potential of landfill mining and resource recovery: Evidence from plant cases, provincial data, and life cycle assessment in China - Ang Wang; Jing Li; Wenxin Xue; Yin Li; Hanqiao Liu; Jifeng Zhao; Qianlong Han (Journal of Environmental Chemical Engineering, 2026)

A proof of concept study of electrocoagulation powered by an electro-wetland for hexavalent chromium removal from wastewater - Xiaorui Lei; Yaqian Zhao; Ting Wei; Yi Mao; Fuhao Zhang; Ang Liu; Yujie Yuan (Chemical Engineering Journal, 2026)

Characteristics and drivers of net ecosystem CO2 exchange in the Badain Jaran Desert - Ping Yang; Hang Zhao; Jinqiao Liu; Qingfan Song; Zhenmin Niu; Nai’ang Wang (Theoretical and Applied Climatology, 2026)

HUTG: a next-generation IGS real‑time combined GIM via two‑step global and regional correction with robust weighting from HENU and UPC‑IonSAT - Kualong Xu; Qi Liu; Manuel Hernández-Pajares; Enric Monte-Moreno; Heng Yang; Germán Olivares-Pulido; David Roma-Dollase; Alberto García-Rigo; Ningbo Wang; Zishen Li; Ang Liu; Clément Ubelmann; et al. (GPS Solutions, 2026)

Wollastonite enhances microbial diversity and ecological network stability - Yanzhi Wang; Yongfeng Wang; Ronghua Kang; Chunjie Tian; Guochen Li; Feifei Zhu; Ang Wang; Geshere Abdisa Gurmesa; Chenxia Su; Chang Liu; Dong Liu; Zhi Quan; et al. (Applied Soil Ecology, 2026)

Topography‐Mediated Soil Moisture Controls Forest Hillslope‐Scale NO and N 2 O Emissions - Kai Huang; Dongwei Liu; Yihang Duan; Di Wu; Geshere Abdisa Gurmesa; Ronghua Kang; Jingwen Xu; Xue Li; Yuqi Liu; Erik A. Hobbie; Xiaoming Fang; Chenxia Su; et al. (Global Change Biology, 2026)
Temperate forests are key terrestrial carbon sinks, yet their capacity to sequester carbon is often limited by nitrogen (N), a nutrient whose availability is declining in many ecosystems. Among factors contributing to declining N availability, climate‐driven changes in soil hydrology could force N loss via the emission of both nitric oxide (NO) and nitrous oxide (N 2 O); however, forecasting these losses is challenging because they are regulated by soil moisture, a factor that regulates microbial activity and substrate availability but varies significantly across space and time. Here, we ask: how do topography‐driven soil moisture gradients and changes in seasonality (e.g., spring–thaw cycles) mediate hillslope‐scale N emissions? We measured over 2 years of high‐resolution in situ NO and N 2 O fluxes from 16 automated chambers deployed along a topographic gradient in a temperate forest to show that soil moisture gradients governed spatial and temporal patterns of soil N emissions. These gradients produced tradeoffs in process controls, whereby temperature regulated N emissions in drier upper positions, giving way to soil moisture regulating microbial pathways and emissions in wetter downslope positions. We then used these relationships among soil moisture, temperature, and N availability to develop models for predicting hillslope‐scale NO + N 2 O losses. Annual emissions averaged 0.2 kg NO‐N ha −1 (range: 0.1–0.3) and 1.0 kg N 2 O‐N ha −1 (range: 0.7–4.9), with N 2 O showing a stronger response to moisture‐driven changes than NO. The spring freeze–thaw period accounted for 15%–26% of NO and 24%–58% of N 2 O annual emissions, with the highest emissions measured consistently at lower topographic positions. These findings establish topography‐mediated hydrology as a primary control of forest soil N dynamics and gaseous N emissions, reducing uncertainty in forecasts of hillslope‐scale N losses under a changing climate.

The DNA-binding protein PfAP2-V regulates erythrocyte invasion and pathogenesis of the human malaria parasite Plasmodium falciparum - Yanxin Zhang; Changhong Wang; Qilong Li; Ang Li; Yutao Zhang; Ziwei Su; Liying Yu; Kexin Zheng; Tong Liu; Ning Jiang; Yiwei Zhang; Xiaoyu Sang; et al. (Science China Life Sciences, 2026)

Mechanisms of 1-methylcyclopropene (1-MCP) in regulating ethylene signal transduction and its role in stress responses: A review - ShiMing Guo; KaiYi Xue; ShaoYan Si; JianWen Gu; Li Liu; WeiLan Yan; Ang Zhang; PengFei Ren; Xin Du (Plant Science, 2026)

Ecological risk and source apportionment of heavy metals in surface sediments from a key shellfish production area in Northern Liaodong Bay, China - Ang Li; Suyan Xue; Muzhan Sun; Qingbin Ma; Jiaqi Li; Lulei Liu; Ling Zhu; Yuze Mao (Marine Environmental Research, 2026)

Exploring advanced measures of constructed wetland for the improved removal of emerging contaminants - Ang Liu; Yaqian Zhao; Jiwei Zhu; Ting Wei; Kaiyue Hao; Liu Yang; Carlos A. Arias; Juan A. Baeza (Journal of Environmental Management, 2026)

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

Preparation and Adsorption Performance of Composite Activated Carbon from Organic Sludge and Biomass - Suqing Lu; Ang Wang; Yin Li; Yanqin Guo; Hanqiao Liu (Water, Air, & Soil Pollution, 2026)

Migration of the post-middle holocene mud depocenter off the Zhejiang coast around 2 ka and its controlling mechanism - Jiandong Qiu; Jian Liu; Rongrong Cheng; Yoshiki Saito; Ang Li; Ke Cao; Yuan Tian; Bin Chen; Zhe Xu; Meina Li (Geo-Marine Letters, 2026)

A Global Conservation Blind Spot: Neglect of Bryophytes Undermines Biodiversity Targets - Xiangbo Yin; Yifei Liu; Fanhao Kong; Lei Shu; Changlian Peng; Lee Ping Ang (Global Change Biology, 2026)
The global biodiversity crisis is unevenly documented, with conservation assessments heavily biased toward vertebrates and flowering plants. Terrestrial gametophyte‐dominant plants (i.e., bryophytes), with over 20,000 species and representing one of Earth's oldest radiations, remain among the most overlooked. To quantify this gap, we integrated global distribution records, elevation patterns, IUCN datasets, research trends, and threat meta‐analyzes. Thirty‐seven bryophyte‐rich regions and global elevational patterns were identified. We found only 1.5% of bryophyte species have been assessed by the IUCN Red List, and among these assessed species, over half are threatened, nearly twice the global average for plants. Agriculture and climate change emerged as the dominant extinction drivers worldwide, while threats vary regionally: deforestation threatens bryophyte diversity in Africa and South America, while climate change and invasive species are the primary threats in Europe. Without targeted, region‐specific conservation strategies, accelerating bryophyte decline will undermine biodiversity targets and jeopardize essential ecosystem functions.

Reply to Wang, L.; Fan, B. Golden Pompano in China Is Trachinotus anak, Not T. ovatus. Comment on “Li et al. DNA Barcode and Correct Scientific Name of Golden Pompano, an Important Marine Aquaculture Fish Species in China. Fishes 2025, 10, 129” - Ang Li; Changting An; Huan Wang; Shuai Che; Shufang Liu; Zhimeng Zhuang (Fishes, 2026)
In a recent study [...]

Superoxide mediated Mn(II) oxidation of an alkali-tolerant bacterium Pseudorhizobium flavum MXJ-1 - Haixia Pan; Fei Li; Ruiying Zhang; Yu Liu; Jieyi Li; Tongtong Wu; Ang Li; Hao Zhou (Journal of Environmental Sciences, 2026)

Functional Roles and Regulatory Factors of Histidine-Related Compounds in Skeletal Muscle Metabolism of Teleosts with Distinct Swimming Strategies - Huan Wang; Jiefeng Li; Ang Li; Changting An; Shuai Che; Shengcong Liu; Shufang Liu; Zhimeng Zhuang (Marine Biotechnology, 2026)

Real-time versus postprocessing IGS combined global TEC maps: examined by Jason-3 altimetry and DORIS observations - Ang Li; Ningbo Wang; Zishen Li; Ang Liu; Yang Li; Liang Wang; Bingcheng Liu (GPS Solutions, 2026)

Determination of multi-GNSS differential code biases with satellite antenna phase center corrections - Ningbo Wang; Yang Li; Zishen Li; Ang Liu; Bingcheng Liu (GPS Solutions, 2026)

Spatiotemporal analysis of global broadcast ionospheric model accuracy for GNSS systems during 2023–2024 solar maximum period - Xiangyi Zhang; Hongliang Cai; Qiang Zhang; Ang Liu; Chenghe Fang; Ji Guo (Advances in Space Research, 2026)

Combined effects of marine heatwaves and nano-titanium dioxide (nano-TiO₂) on the physiological fitness in the mussel Mytilus coruscus - Bing Liu; Menghong Hu; Li'ang Li; Mojiang Zhang; Xinyue Li; Mohamed H. Abo-Raya; Youji Wang (Marine Pollution Bulletin, 2026)

Impact and assessment of hydraulic rake trawling on benthic communities in Urechis unicinctus aquaculture zones, Laizhou Bay, China - Yuze Tang; Erwann Legrand; Jiaqi Li; Haiqing Wang; Ang Li; Lulei Liu; Zirong Liu; Suyan Xue; Shoutuan Yu; Yuze Mao (Ocean & Coastal Management, 2026)

Mono(2-ethylhexyl) phthalate activates JNK signaling via TLR4-MD2 binding to induce podocyte injury in chronic kidney disease - Jiajun Jing; Shaohui Liu; Li Yan; Li'e Zhang; Qiuju Liang; Yuting Wen; Xiaofeng Huang; Zijuan Qi; Mingjun Wang; Zi'ang Huang; Sijin Liu; Yunfeng Zou; et al. (Journal of Hazardous Materials, 2026)

Dual single sites of single metal atom and molecule ligand on TiO₂ atomic-scale step to boost photocatalytic CO2 reduction - Yuxin Liu; Yang Wang; Yibo Feng; Peixin Cui; Kaiwen Wang; Zhouhao Zhu; Xiaoyuan Zhou; Liyong Gan; Shengqi Chu; Guangcai Chang; Ang Li; Xiaodong Han; et al. (Chemical Engineering Journal, 2026)

Synergistic 3d-5d orbital interactions on oxygen vacancy-rich Pt/TiO2 for enhanced photothermal catalytic oxidation of propylene - Xiaoxiao Zhu; Weidong Yuan; Siyi Song; Tong Chen; Wenjun Xiong; Sibo Wang; Jinpeng Hu; Rui Liu; Zhu Luo; Jinlong Wang; Ang Gao; Yanbing Guo (Chemical Engineering Journal, 2026)

A unified intracellular pH landscape with SITE-pHorin: a quantum-entanglement-enhanced pH probe - Shu-Ang Li; Xiao-Yan Meng; Su Zhang; Ying-Jie Zhang; Run-Zhou Yang; Dian-Dian Wang; Yang Yang; Pei-Pei Liu; Jian-Sheng Kang (Science China Life Sciences, 2026)

Genome Sequence Analysis Reveals Polyphyly in the Genus Pseudaestuariivita and Supports Reclassification of the Species Pseudaestuariivita rosea as Parasulfitobacter roseus comb.nov - Mengdan He; Xiaokun Xu; Qingjie Xue; Ang Liu (Current Microbiology, 2026)

Molecular authentication of Gekko gecko using multienzyme isothermal rapid amplification technology - Jinjun Chai; Yating Zhang; Yuxin Xie; Ziqiang Xu; Ang Liu; Yi Yang; Lijun Gao; Wei Xia (Analytica Chimica Acta, 2026)

Effects of curcumin and Curcuma longa extract on inflammatory biomarkers in patients with rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE): a systematic review and meta-analysis of randomized controlled trials - Ang-Jun Liu; Po-Chang Wu; Yu-Pei Chen; Hsueh-Ting Chu; Hen-Hong Chang (Inflammation Research, 2025)

Synergistic lipid-lowering effects of Monascus purpureus and honeysuckle co-fermentation products: Insights from metabolomics, network pharmacology, and cellular experiments - Arzugul Ablimit; Qing Sun; Mengxue Chen; Huijun Dong; Wenbo Liu; Yike Zhai; Duchen Zhai; Ang Huang; Dingrong Kang; Baoguo Sun; Chengtao Wang; Chan Zhang (Food Bioscience, 2025)

Boosting the plateau capacity via phosphoric acid cross-linking strategy for phenolic resin-based hard carbon - Xiaoqi Yu; Xiaoyu Xu; Hanyu Wei; Haiyan Liu; Ang Li; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2025)

Measurement and modeling of sorption-induced coal matrix deformations with considering isosteric heat of adsorption - Kunming Zhang; Ang Liu; Shimin Liu (Chemical Engineering Journal, 2025)

Biochar-mediated electron transfer in a spinel ferrite catalyst boosts peracetic acid activation for water decontamination - Lu Xia; Xinlan Li; Zhuojun Wei; Ang Liu; Jianqiu Chen; Jingge Shang (Chemical Engineering Journal, 2025)

Fluorine-doping and biomass nanocellulose synergy enable ultra-stable ZnMn2O4 cathodes for aqueous zinc-ion batteries - Zi'ang Quan; Kaiqiang Zheng; Juan Liu; Yingbo Zang; Di Gao; Meng Cui (Chemical Engineering Journal, 2025)

Wollastonite improves soybean yield without toxic trace elements enrichment - Yanzhi Wang; Ji Chen; Guochen Li; Chao Gong; Ang Wang; Ronghua Kang; Feifei Zhu; Jiaoyue Wang; Chang Liu; Dong Liu; Chenxia Su; Quanping Zhang; et al. (Nutrient Cycling in Agroecosystems, 2025)

Validating recent global canopy height maps over China's forests based on UAV lidar data - Ang Chen; Kai Cheng; Yuling Chen; Zhiyong Qi; Haitao Yang; Yu Ren; Zekun Yang; Mengxi Chen; Jiachen Xu; Yixuan Zhang; Guoran Huang; Tianyu Xiang; et al. (Remote Sensing of Environment, 2025)

Effects of Per- and polyfluoroalkyl substances on atherosclerosis: an evidence-based risk assessment in the context of the TRAEC strategy - Yiming Zhu; Zhenzhen Tan; Ziwen An; Longfei Li; Mingmei Guo; Wenjing Duan; Zhixia Yu; Ziang Chen; Yi Liu; Ang Li; Huicai Guo (Environmental Research, 2025)

Scale-factor-based regional zenith tropospheric delay modeling for real-time precise point positioning - Hao Chen; Ningbo Wang; Zishen Li; Kefei Zhang; Suqin Wu; Peng Sun; Ang Liu; Gongwei Xiao (Advances in Space Research, 2025)

Increasing alkalinity to mitigate biogenic acidification and its negative effects during the North–south-relay transportation of abalone - Jiamin Li; Jiaqi Li; Yitao Zhang; Minghui Jiao; Ang Li; Zirong Liu; Zhongzhi Shen; Suyan Xue; Lulei Liu; Yuze Mao (Aquaculture International, 2025)

New insights into the interaction between nanocolloid of graphene oxide and dissolved organic matter: Spectroscopic methods and density functional theory calculations - Ang Liu; Tuantuan Fan; Weibo Zhang; Xihuan Wang; Zhong Jin; Zeya Zhang; Peng Xia; Fei Guo; Chenglian Feng; Yingchen Bai (Journal of Hazardous Materials, 2025)

Chemical analysis of mulberry (Morus alba L.) leaves treated with jasmonates on nutrition composition and biological activity - Zhi-Ang Zhang; Jia-Ying Liu; Jia-Le Tian; Marriam Khurshid; Cheng-Hai Yan; Richard Ansah Herman; Lu-Chan Gong; Jun Wang (Food Chemistry, 2025)

Temporal dynamics of gonadal development and reproduction of wild Manila clam (Ruditapes philippinarum) in the Xiaoqing River estuary, Laizhou Bay - Lulei Liu; Suyan Xue; Ang Li; Yushui Ren; Ling Zhu; Jiaqi Li; Longzhen Liu; Yuze Tang; Yanguo Qiu; Yuze Mao (Estuarine, Coastal and Shelf Science, 2025)

Rational design of SnO2 quantum dots/SnS2 hybrids for enhanced NO2 sensing at room temperature: Insights from DFT and in-situ DRIFTS - Jinzhou Bai; Yanbai Shen; Ang Li; Meili Wu; Siyao Liu; Wenbao Liu; Qiang Zhao; Sikai Zhao; Fanli Meng (Chemical Engineering Journal, 2025)

Waterworks sludge coupled with biochar and pyrite as wetland substrates for enhanced nitrogen removal and greenhouse gases mitigation: First study on synergistic mechanisms - Yujie Yuan; Yaqian Zhao; Tao Zhang; Ting Wei; Yamei Cai; Lei Yang; Jingmiao Fu; Ang Liu; Anran Yang (Chemical Engineering Journal, 2025)

Hierarchical micro/mesopore-enriched, extra-high surface area activated carbon from coffee grounds for enhanced performance in electrical double layer capacitors - Ying-Hsuan Liu; Hamed Pourzolfaghar; Tai Le -Thanh; Amornrat Srithongpusakul; Gavin Pomoung; Apisara Kittipoomwong; Jia-Qing Liao; Ang-You Hsieh; Yuan-Yao Li (Biomass and Bioenergy, 2025)

Coal Sample Dynamics Experiment under the Combined Influence of Cyclic Dynamic Load and Gas Pressure: Phenomenon and Mechanism - Siqing Zhang; Xiaofei Liu; Zhoujie Gu; Xiaoran Wang; Xin Zhou; Ang Gao (Natural Resources Research, 2025)

Morphological characteristics and evolution of stream potholes in the Quanfengtan reach of the Lower Zijiang River, Hunan Province, China - Linhong Chen; Fenliang Liu; Nan Ding; Junhua Huang; Yu’ang Liu; Hongshan Gao (Journal of Mountain Science, 2025)

Sustainable fill solutions: recycling EPS waste in shredded EPS-clayed soil composites for improved mechanical and compaction behaviour - Muhammad Haseeb; Zain Maqsood; Muhammad Baqir; Sofia Sarwar; Badee Alshameri; Waqas Hassan; Abbas Haider; Lin Wenli; Mehtab Alam; Jiren Xie; Liu Ang; Muhammad Umar (Transportation Geotechnics, 2025)

Recent advances of constructed wetlands utilization under cold environment: Strategies and measures - Kaiyue Hao; Yaqian Zhao; Ting Wei; Du Wen; Ang Liu; Yulong Huang; Zhenzhen Chen (Process Safety and Environmental Protection, 2025)

Intestinal microbiota responses to environmental microbiomes and factors across populations of the Manila clam Ruditapes philippinarum - Longzhen Liu; Lulei Liu; Haonan Zhuang; Ang Li; Zirong Liu; Minghui Jiao; Jiamin Li; Suyan Xue; Jiaqi Li; Yushui Ren; Yuze Mao (Marine Environmental Research, 2025)

Femtosecond laser-induced myocardial incision: Preclinical study towards new tools for precision cardiac surgery - Ang Liu; Tong Xia; Siyuan Cao; He Zhao; Yubin Hou; Xuejing Duan; Li Li; Ke Wang; Pu Wang; Chaowu Yan (Journal of Photochemistry and Photobiology B: Biology, 2025)

Association between per- and polyfluoroalkyl substances with serum hepatobiliary system function biomarkers in patients with acute coronary syndrome - Fang Xiao; Ming Yang; Junli Lv; Jing Li; Mingmei Guo; WenJing Duan; Haoran Li; Ziwen An; Zhengyi Su; Ang Li; Yi Liu; Jingchao Lu; et al. (Journal of Environmental Sciences, 2025)

Transmission of ultrasonic wave across moisture rocks: Effects of moisture sorption on velocity variation and attenuation - Ang Liu; Guijie Sang; Shimin Liu; Xing Li; Gang Wang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Integrated multiscale topology optimization of frame structures for minimizing compliance - Kui Liu; Kirk Ming Yeoh; Yehui Cui; Ang Zhao; Yangjun Luo; Zheng Zhong (Engineering Structures, 2025)

Quantifying graphitic curvature and engineering closed pores in phenolic resin hard carbons for enhanced plateau capacity in sodium-ion batteries - Xiaotian Li; Jiapeng Zhang; Renlu Yuan; Boyang Zhao; Chuang Qiu; Dengke Wang; Man Yuan; Ang Li; Haiyan Liu; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2025)

Nickel-doped ZIF-L as a high-performance catalyst for peroxymonosulfate activation and singlet oxygen-mediated As(III) removal - Jian Ye; Chuang Li; Zhiming Yang; Xuan Hu; Qiang Chen; Ang Sun; Mingyang Dai; Shaobo Liu; Chunping Yang (Journal of Environmental Chemical Engineering, 2025)

Variability of urinary metal in short-, mid-, long-term periods and its optimal sampling strategy: A novel epidemiological insight to exposure classification - Yanbing Li; Liu Liu; Yayuan Mei; Jiaxin Zhao; Quan Zhou; Kai Li; Ming Yang; Lingli Sun; Ang Li; Qun Xu (Environmental Research, 2025)

A patient-friendly sprayable rapid gelation powder (SRGP) with prolonged mucoadhesion for oral ulcer therapy - Jingyi Liu; Songbai Zhang; Jinteng Feng; Zhe Feng; Min Zhang; Ang Li; Feng Xu; Haoyu Wang; Dandan Pei; Yuanbo Jia (Chemical Engineering Journal, 2025)

Ocean acidification shifts carbonate chemistry heterogeneity in molluscan respiratory microenvironments - Minghui Jiao; Jiaqi Li; Meng Zhang; Jiamin Li; Zibing Hao; Haonan Zhuang; Yujia Zhou; Ang Li; Longzhen Liu; Suyan Xue; Lulei Liu; Yuze Mao (Marine Pollution Bulletin, 2025)

The PpAHL17-PpHYH module is involved in light-independent anthocyanin accumulation in fruit peel of Prunus persica - Xiaoyu Zhang; Shihang Sun; Xin Liu; Junren Meng; Mingzhu Yuan; Ang Li; Wenyi Duan; Lei Pan; Zhiqiang Wang; Wenfang Zeng; Liang Niu (Plant Cell Reports, 2025)

Cerium oxide nanoparticles as potent inhibitors of ferroptosis: role of antioxidant activity and protein regulation - Chenran Feng; Tong Yang; Jie Zhou; Chen Wang; Zheng Chu; Ying Zhang; Junzhe Zhang; Yin Kwan Wong; Cui Liu; Peng Gao; Ang Ma; Huan Tang; et al. (Journal of Molecular Medicine, 2025)

Targeting myeloid differentiation protein 2 ameliorates rheumatoid arthritis by inhibiting inflammation and ferroptosis via MAPK and NF-κB signaling pathways - Lirun Zhou; Tong Yang; Shujie Zhang; Dandan Liu; Chenran Feng; Jiang Ni; Qiaoli Shi; Yanqing Liu; Yuqing Meng; Yongping Zhu; Huan Tang; Jigang Wang; et al. (Journal of Molecular Medicine, 2025)

Sufficient burial depth is a prerequisite for Chinese cyclina (Cyclina sinensis) to maintain normal life activities - Yurou Ma; Shiyu Yan; Zhengyu Shao; Guolong Zhou; Ang Hu; Yawei Bu; Huimin Wang; Xinqi Lv; Jianyu Liu; Yihua Chen; Zhiguo Dong (Aquaculture, 2025)

Mg/Ca and Sr/Ca ratios of Limnocythere inopinata ostracod valves from the Badain Jaran Desert, Northwest China and their implications for paleoenvironmental reconstruction - Gaolei Jiang; Linjing Liu; Xin Mao; Zhongshuang Cheng; Zhe Wang; Meng Li; Nai'’ang Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Degradation of o-DCB and dioxins by MnCe catalysts prepared via the mechanochemical method - Fan Yao; Yaqi Peng; Zhiyuan Gong; Ling Wang; Hongxian Li; Qi Liu; Guanjie Wang; Minghui Tang; Ang Cao; Shengyong Lu (Journal of Environmental Chemical Engineering, 2025)

Vertical characteristics of bacterial community and the interaction of dissolved organic matter in sediments of a shallow lake, China - Xihuan Wang; Weibo Zhang; Ang Liu; Zhong Jin; Yili Fan; Zeya Zhang; Chenglian Feng; Yingchen Bai (Journal of Environmental Chemical Engineering, 2025)

Utilization and perspectives of electricity generated from electro-wetland - Xiaorui Lei; Yaqian Zhao; Asheesh Kumar Yadav; Ang Liu; Yi Mao; Dan Wei; Fuhao Zhang; Xuechen Bai; Pratiksha Srivastava (Journal of Environmental Chemical Engineering, 2025)

Inorganic and organic constituent analysis: A data fusion strategy to differentiate between wines of different origins - Yingyue Su; Zhaoxiang Wang; Qianqian Liu; Yuyu Li; Cui Zhang; Xiaohui Feng; Ang Zhang; Chunlong Yuan (Food Control, 2025)

Cohort Profile: Precision Environmental Health Cohort of Healthy Undergraduates - Yanbing Li; Yayuan Mei; Jiaxin Zhao; Quan Zhou; Kai Li; Ming Yang; Liu Liu; Huicai Guo; Qun Xu; Ang Li (Phenomics, 2025)

Water Use Efficiency of Grassland Ecosystem in Badain Jaran Desert and Its Relations to Biometeorological Variables - Nan Meng; Nai’ang Wang; Liqiang Zhao; Xiaojun Liu; Jinqiao Liu; Sung-Ching Lee (Ecosystems, 2025)

Molecular detection and genotyping of bovine viral diarrhea virus in four provinces of China - Ying Liu; Feng Zhou; Xuan-ang Wang; Xi-Meng Chen; Lan-Lan Zheng; Hong-Ying Chen; Shi-Jie Ma (Archives of Virology, 2025)

Biological functions and molecular mechanisms of circHIPK3 in digestive system tumors - Jian Li; Xin Su; Xiao Xu; Youbao Ye; Cailiu Wang; Ang Liu; Changchun Zhao; Wenxiu Liu; Liwen Yang; Tao Wang; Xiangyong Hao (Human Cell, 2025)

Comparative analysis of femtosecond, picosecond, and nanosecond laser techniques for transseptal puncture: An in vitro study with pathological correlation - Ang Liu; Tong Xia; Siyuan Cao; He Zhao; Yubin Hou; Xuejing Duan; Li Li; Ke Wang; Pu Wang; Chaowu Yan (Journal of Photochemistry and Photobiology B: Biology, 2025)

Quantifying and modeling of coal permeability spatiotemporal response: Implications for gas recovery and CO2 sequestration - Jinming Zhang; Xiaowei Hou; Shimin Liu; Yanming Zhu; Ang Liu; Long Fan; Yingjin Wang; Han Zhang (Fuel, 2025)

Probing the microwave induced overheating at electrode surface using a combined electrochemical and fluorescence method - Zongliang Kou; Zhenyu Zhao; Hong Li; Ang Li; Kai Liu; Xiaolei Fan; Xin Gao (Chemical Engineering Journal, 2025)

Spatial configuration engineering of phenolic resins to tune the closed pores of hard carbon for enhanced plateau-capacity sodium storage - Liewen Guo; Chuang Qiu; Haiyan Liu; Renlu Yuan; Xiaotian Li; Xin Li; Kairan Li; Wanxiong Zhu; Mohammad Tabish; Xuewei Liu; Ang Li; Xiaohong Chen; et al. (Chemical Engineering Journal, 2025)

High content of single-atomic sulfur in nano carbon spheres boosting potassium storage performance - Bin Cao; Zirong Guo; Huan Liu; Yu Ma; Wei Zhao; Yiheng Yang; Ang Li; Huaihe Song; Yaxiong Yang; Zhenglong Li; Wubin Du (Chemical Engineering Journal, 2025)

Investigations of spatial-temporal distribution and regional transport in typical section of NO2 in eastern China using Mobile-DOAS - Zhidong Zhang; Pinhua Xie; Ang Li; Jin Xu; Xin Tian; Feng Hu; Zhaokun Hu; Yinsheng Lv; Youtao Li; Qiang Zhang; Wenqing Liu (Science of The Total Environment, 2025)

Study on the genesis of carbonate cements in tight and non-tight sandstone reservoirs in Fukang Sag - Li Na; Wang Zi'ang; Liu Gang; Wang Guozhi; Huang Sheng; Liu Jinlong; Jing Yang; Chen Haixia (Ore and Energy Resource Geology, 2025)

Role of per- and polyfluoroalkyl substances in the cardiorenal system: Unraveling crosstalk from the network of pollutants and phenotypes - Ming Yang; Jiaxin Zhao; Ziwen An; Haoran Li; Chaoying Ma; Junli Lv; Fang Xiao; Zhenzhen Tan; Longfei Li; Xiaoguang Zhang; Xuehui Liu; Yi Liu; et al. (Journal of Environmental Sciences, 2025)

High-Voltage aqueous supercapacitors based on l-lysine pH Self-Buffering Coating-modified carbon cloth electrode - Ang Xu; Jie Gao; Huan Li; Xiyu Song; Bo Xu; Ying Liu; Yuanyuan Yu; Ping Wang; Qiang Wang; Man Zhou (Chemical Engineering Journal, 2025)

Dynamic engineering of lithiation reactions in silicon oxide with interface regulation for enhanced safety in lithium-ion batteries - Tianxiang Yang; Yisha Wang; Liu Yang; Hanqi Zhang; Mingtong Zhang; Edison Huixiang Ang; Jixin Zhu (Chemical Engineering Journal, 2025)

Identification of elite alleles associated with glume-opening angle in rice natural population - Yingying Zhao; Hui Jiang; Chunyu Jing; Tianhu Li; Yanan Zhang; Zhengbo Liu; Yinping Chang; Mingyu Du; Hao Sun; Jinghan Sun; Yang Ang; Xianping Cheng; et al. (Euphytica, 2025)

Characterizing PPP ambiguity resolution residuals for precise orbit and clock corrections integrity monitoring - Mingqiang Xie; Ningbo Wang; Ahmed El-mowafy; Zishen Li; Ang Liu; Dongyan Wei (GPS Solutions, 2025)

DNA Barcode and Correct Scientific Name of Golden Pompano, an Important Marine Aquaculture Fish Species in China - Ang Li; Changting An; Huan Wang; Shuai Che; Shufang Liu; Zhimeng Zhuang (Fishes, 2025)
The golden pompano ranks at the top of production in current China’s marine fish aquaculture; however, there has been long-standing controversy regarding its valid scientific name. Multiple latin names were used simultaneously to refer to golden pompano, such as Trachinotus ovatus, T. blochii, T. mookalee and T. anak. Moreover, two distinct morphological species are regarded as deserving the scientific name T. ovatus. In this study, we employed DNA barcoding to determine which particular species the “golden pompano” represents and to explore the potential synonyms and cryptic species within T. ovatus and its closely related species. We analyzed the DNA barcodes of golden pompano samples from various aquaculture farms in China’s main production regions, as well as most species within the genus Trachinotus. The phylogenetic analyses revealed that all T. ovatus sequences clustered into two divergent clades with a large genetic distance, and the two clades were geographically separated, being from the Indo-west Pacific and the East Atlantic regions, respectively. Based on the type locality information and historical distribution records, we support the validity of the naming of Trachinotus ovatus from the Indo-west Pacific, and the so-called Trachinotus ovatus from the East Atlantic may represent a cryptic species. All the golden pompano samples were clustered into the Indo-west Pacific T. ovatus clade, with a considerably small intragroup genetic distance, which suggests that the golden pompano in China should be identified as the species Trachinotus ovatus. The golden pompano, T. blochii and T. mookalee were completely separated into distinct monophyletic clades in the phylogenetic trees, which indicated that they are different species. The T. anak clustered with the monophyletic clade of Indo-west Pacific T. ovatus and the genetic distance between them was at the intraspecific difference level. This implied that the T. anak might be the junior synonym of T. ovatus. The species delimitations based on the ABGD and bPTP methods are in agreement with the findings from phylogenetic analyses. The above results help to form a consistent viewpoint regarding the naming of the golden pompano and provide new understandings for the taxonomy of the genus Trachinotus.

Deciphering structure-rheological properties relationship via the studies of 11 s-rich and 7 s-rich soy protein isolate - Binyu Luan; Ang Meng; Wenjing Zhang; Fengqiujie Wang; Feng Liu; Weichun Pan; Xiuqing Zhu; Bo Zhang (Food Chemistry, 2025)

Integrated metabolomic and transcriptomic analysis reveals the regulatory effects of IAA on polyphenol biosynthesis and antioxidant activity in Phlebopus portentosus - Taobo Xiang; Feng Ge; Lei Zhu; Gaige Shao; Tao Wu; Hao Fan; Yueqian Liu; Longyu Wang; Jing Wang; Peng Li; Qin He; Ailiang Jiang; et al. (Food Bioscience, 2025)

Development of red grapefruit jam fermented with Monascus purpureus: Effect of naringenin on Monascus purpureus growth and metabolism - Chan Zhang; Congcong Wang; Arzugul Ablimit; Mengxue Chen; Qing Sun; Huijun Dong; Wenbo Liu; Ang Huang; Bobo Zhang; Wenlin Hu; Chengjian Liu; Chengtao Wang (Food Bioscience, 2025)

Wet deposition of atmospheric Hg in a typical inland city in North China: Sources, influencing factors, and health risk assessment - Xiaofei Li; Wen Yang; Fei Gao; Ang Li; Lekhendra Tripathee; Junming Guo; Lang Liu (Environmental Pollution, 2025)

Size effect in shear failure of RC beams reinforced with CFRP sheets: Influences of CFRP adhesion angle and shear-span ratio - Liu Jin; Peng Qin; Jiangxing Zhang; Dong Li; Xuan-ang Jiang; Xiuli Du (Engineering Structures, 2025)

Mitochondrial biogenesis microcarriers break membrane barriers for endogenous nucleus pulposus repair - Xiaohu Li; Hongze Chang; Libin Pang; Ang Li; Juan Wang; Yi Yu; Honglei Xiao; Zhengwei Cai; Wenguo Cui; Xiaodong Liu (Chemical Engineering Journal, 2025)

Phellodendrine Exerts Protective Effects on Intra-abdominal Sepsis by Inactivating AKT/NF-kB Signaling - Ang Li; Peng Liu; Jiaohong Gan; Weijun Fang; Anjie Liu (Cell Biochemistry and Biophysics, 2025)

Tissue accumulation and hepatotoxicity of 8:2 chlorinated polyfluoroalkyl ether sulfonate: A multi-omics analysis deciphering hepatic amino acid metabolic dysregulation in mice - Zhenzhen Tan; Ziwen An; Junli Lv; Fang Xiao; Longfei Li; Jing Li; Wenjing Duan; Mingmei Guo; Xiuli Zeng; Yi Liu; Ang Li; Huicai Guo (Journal of Hazardous Materials, 2025)

Effect of the LIF gene on the cell cycle and apoptosis of ovarian granulosa cells in white Muscovy ducks - Qing-hua Tao; Ning-ning Sun; Meng-shi Wang; Wan-xin Zhao; Wei Liu; Xu Zhang; Ang Li (Theriogenology, 2024)

Microalgae create a highway for carbon sequestration in livestock wastewater: Carbon sequestration capacity, sequestration mechanisms, influencing factors, and prospects - Han Wang; Jiahua Liu; Khinkhin Phyu; Yu'ang Cao; Xiaoyu Xu; Junfeng Liang; Chein-Chi Chang; Keqiang Zhang; Suli Zhi (Science of The Total Environment, 2024)

Efficient green synthesis of biocompatible MPN fluorescent microspheres via hydrophobic-force-driven strategy for enhanced immunochromatographic assays - Xiaocui Lai; Shijin Huang; Ganggang Zhang; Edison Huixiang Ang; Hongxin Yuan; Liu Su; Cong Liu; Shengliang Deng; Weihua Lai (Journal of Hazardous Materials, 2024)

Legacy and alternative per- and polyfluoroalkyl substances spatiotemporal distribution in China: Human exposure, environmental media, and risk assessment - Jing Li; Wenjing Duan; Ziwen An; Zexuan Jiang; Longfei Li; Mingmei Guo; Zhenzhen Tan; Xiuli Zeng; Xuehui Liu; Yi Liu; Ang Li; Huicai Guo (Journal of Hazardous Materials, 2024)

Advanced membrane contactor coupled with electrodialysis metathesis for efficient carbon dioxide capture and waste salt remediation - Yundi Dong; Yangbo Qiu; Haili Wei; Chunhong Liu; Ke Wu; Junbin Liao; Edison Huixiang Ang; Jiangnan Shen (Desalination, 2024)

Traffic signal-inspired fluorescence lateral flow immunoassay utilizing self-assembled AIENP@Ni/EC for simultaneous multi-pesticide residue detection - Xiaocui Lai; Wenkai Cao; Ganggang Zhang; Edison Huixiang Ang; Liu Su; Cong Liu; Weihua He; Weihua Lai; Shengliang Deng (Chemical Engineering Journal, 2024)

Synergistic regulation of dual thresholds: Hydroxyl occupancy and carbon species in the targeted catalytic hydrocracking of lignite - Cong Liu; Zhi-Ang Liu; Zhong-Qiu Liu; Hai-Ni Yang; Guo-Xiao-Yao Zhao; Yujing Liu; Anguo Ying (Chemical Engineering Journal, 2024)

Large-scale oyster farming accelerates the removal of dissolved inorganic carbon from seawater in Sanggou Bay - Jiaqi Li; Zengjie Jiang; Meng Zhang; Xin Sun; Minghui Jiao; Jiamin Li; Suyan Xue; Ang Li; Longzhen Liu; Ling Zhu; Yuze Mao (Marine Environmental Research, 2024)

Formation mechanism and geophysical properties of fracture-filling gas hydrate in the host sediments: A comprehensive review - Gaowei Hu; Zhun Zhang; Yapeng Zhao; Qingtao Bu; Ang Li; Wengao Zhao; Zihao Wang; Xiaoqian Qiu; Tong Liu; Shengbiao Liu; Wanjun Lu; Nengyou Wu (Earth-Science Reviews, 2024)

Exploration of adsorption properties of organic corrosion inhibitors on layered double hydroxide nanosheet: A molecular dynamics simulation study - Haoran Guo; Qingyin Tang; Pan Wang; Muhan Wang; Yue Zhang; Ang Liu; Dongshuai Hou (Applied Clay Science, 2024)

Review on recent advances in supported metal catalysts for synthesis of high energy density fuels - Tian Li; Dandan Jia; Shenglan Zhou; Zhiyuan Liu; Juan Chen; Tao Ban; Ang Li; Haijian Li; Hongyi Gao (Fuel, 2024)

Effect of step-change of solar radiation on human thermal response under non-air-conditioned environments in winter: A field study - Meilan Tan; Yi Liu; Shaocong Wang; Fan Peng; Ang Wang; Bin Zhou (Energy and Buildings, 2024)

Probabilistic evaluation method for the stability of large underground cavern considering the uncertainty of rock mass mechanical parameters: A case study of Baihetan underground powerhouse project - Guofeng Liu; Chi Zhou; Kun Feng; Quan Jiang; Shengfeng Li; Han Bao; Ang Li (Engineering Geology, 2024)

Mixed microalgal culture enhances biofilm adhesion during treatment of livestock wastewater: The role of extracellular polymeric substances - Jiahua Liu; Zengjun Yang; Khinkhin Phyu; Yu’ang Cao; Han Wang; Xiaoyu Xu; Junfeng Liang; Keqiang Zhang; Chein-Chi Chang; Suli Zhi (Chemical Engineering Journal, 2024)

Spermidine protects cartilage from IL-1β-mediated ferroptosis - Qi Cheng; Li Ni; Ang Liu; Xiaoxiong Huang; Pan Xiang; Qin Zhang; Huilin Yang (Molecular and Cellular Biochemistry, 2024)

Association Between Metal Exposure and Mitochondrial DNA Parameters and the Potential Mediation Effect of Oxidative Stress - Jing Xu; Meiduo Zhao; Xiaoyu Ge; Xiaolin Liu; Lanping Wei; Ang Li; Yayuan Mei; Guohuan Yin; Jingtao Wu; Qun Xu (Exposure and Health, 2024)

High-intensity exercise training in large yellow croaker is a compromise between disease resistance and fish welfare - Junjia Zeng; Ang Qu; Yacheng Deng; Pengxin Jiang; Ji Zhao; Jiaying Wang; Yue Liu; Wei Liu; Qiaozhen Ke; Fei Pu; Yaxian Li; Peng Xu (Aquaculture, 2024)

Was there an active continental margin arc along the western margin of Zhangguangcailing Terrane in the eastern Central Asian Orogenic Belt? - Zhaoxu Chen; Boran Liu; Qingbin Guan; Yongjiang Liu; A.Yu. Peskov; Sanzhong Li; Qi’ang Fang (Lithos, 2024)

High valent manganese-oxo species activation of peroxymonosulfate by different phases manganese oxides nanoplates for catalytic water decontamination - Ang Li; Bin Li; Li-Ming Sun; Le-Xuan Liu; Chang Liu; Ya-Meng Dong; Xing Zhang (Chemical Engineering Journal, 2024)

Polydopamine-modulated anisotropic co-growth plasmonic blackbody for efficient ultra-broad-spectrum quenching to establish multicolor fluorescent immunoassay - Xiaocui Lai; Ganggang Zhang; Gan Zhang; Liu Su; Cong Liu; Weihua He; Edison Huixiang Ang; Weihua Lai; Shengliang Deng (Chemical Engineering Journal, 2024)

Research on fine modeling of dispersion fuel plate based on lattice method - Yuqing Chen; Pengfei Liu; Song Li; Lei Lou; Ang Li (Annals of Nuclear Energy, 2024)

Associations between co-exposure to per- and polyfluoroalkyl substances and organophosphate esters and erythrogram in Chinese adults - Ziwen An; Yanbing Li; Jing Li; Zexuan Jiang; Wenjing Duan; Mingmei Guo; Yiming Zhu; Xiuli Zeng; Linfeng Wang; Yi Liu; Ang Li; Huicai Guo; et al. (Chemosphere, 2024)

Identifying climate refugia for wild yaks (Bos mutus) on the Tibetan Plateau - Hang Zhao; Hongyi Cheng; Nai'ang Wang; Liqiong Bai; Xiaowen Chen; Xiao Liu; Bin Qiao (Journal of Environmental Management, 2024)

Biogeochemical changes during supercritical CO2–H2O-coal-microorganism interaction - Wenxing Wang; Weiyu Huang; Wancheng Zhu; Shuyuan Liu; Huiqian Yang; Tecai Li; Yanyan Liu; Ang Li (Gas Science and Engineering, 2024)

Mo4/3B2Tx induced hierarchical structure and rapid reaction dynamics in MoS2 anode for superior sodium storage - Guilong Liu; Wenzhuo Yuan; Zihan Zhao; Jin Li; Naiteng Wu; Donglei Guo; Xiao Liu; Yong Liu; Ang Cao; Xianming Liu (Chemical Engineering Journal, 2024)

Dynamic Mechanical Response and Fracture Characteristics of Multi-flawed Rocks Exposed to Hydrostatic Confinements - Wei You; Feng Dai; Yi Liu; Ang Li (Rock Mechanics and Rock Engineering, 2024)

The structure of bacteria–fungi bipartite networks along elevational gradients in contrasting climates - Wenqian Zhao; Janne Soininen; Ang Hu; Jinfu Liu; Mingjia Li; Jianjun Wang (Molecular Ecology, 2024)
Climate change is altering species distribution and modifying interactions in microbial communities. Understanding microbial community structure and their interactions is crucial to interpreting ecosystem responses to climate change. Here, we examined the assemblages of stream bacteria and fungi, and the associations between the two groups along elevational gradients in two regions with contrasting precipitation and temperature, that is the Galong and Qilian mountains of the Tibetan Plateau. In the wetter and warmer region, the species richness significantly increased and decreased with elevation for bacteria and fungi, respectively, while were nonsignificant in the drier and colder region. Their bipartite network structure was also different by showing significant increases in connectance and nestedness towards higher elevations only in the wetter and warmer region. In addition, these correlation network structure generally exhibited similar positive association with species richness in the wetter and warmer region and the drier and colder region. In the wetter and warmer region, climatic change along elevation was more important in determining connectance and nestedness, whereas microbial species richness exerted a stronger influence on network structure and robustness in the drier and colder region. These findings indicate substantial forthcoming changes in microbial diversity and network structure in warming climates, especially in wetter and warmer regions on Earth, advancing the understanding of microbial bipartite interactions' response to climate change.

Shellfish CO2 excretion is modulated by seawater carbonate chemistry but largely independent of pCO2 - Minghui Jiao; Jiaqi Li; Meng Zhang; Haonan Zhuang; Ang Li; Longzhen Liu; Suyan Xue; Lulei Liu; Yuze Tang; Yuze Mao (Environmental Science and Pollution Research, 2024)

Coral spawning patterns on the Luhuitou fringing reef in Hainan Island of the northern South China Sea - Youfang Sun; Yuyang Zhang; Lei Jiang; Xiaolei Yu; Lintao Huang; Tao Yuan; Jianhui Yang; Jiansheng Lian; Chengyue Liu; Put Ang; Hui Huang (Frontiers in Marine Science, 2024)
Observation of coral spawning times is valuable to detect spawning patterns and identify the potential mechanisms behind coral reproduction. Although large amount of data on global coral spawning records have become available over the past decades, information on coral spawning in the northern South China Sea remains scarce. In this study, we investigated the spawning patterns of scleractinian corals in Luhuitou fringing reef, Hainan Island, China, from 2009 to 2021 in relation to lunar cycles (month and day). The spawning times of 22 coral species from five genera ( Acropora , Montipora , Platygyra , Dipsastraea , and Galaxea ) within three families (Acroporidae, Merulinidae, and Euphylliidae) were recorded, with spawning occurring from lunar February to May 2009–2021. Recorded spawning events started at a period of increasing seawater temperature. Acropora , the most documented genus, spawned between lunar February and April, but primarily in lunar March. Importantly, the spawning time of Acropora was delayed for one lunar month in 2016 most likely due to a rapid decrease in monthly mean seawater temperature in lunar February. Spawning lunar days before, on or after full moon of corals in the Luhuitou Reef, including those of the Acropora species, were highly variable between years even for the same species. No predictable pattern of spawning times can thus be detected. Nonetheless, our results fill up an information gap on coral spawning patterns in the northern South China Sea that may be useful for further understanding of the reproductive biology of scleractinian corals throughout the Indo–West Pacific.

Resourceful application and mechanism of oyster shell-microalgae synergistic system：Sustainable treatment of harsh low carbon nitrogen ratio actual wastewater - Yanni Geng; Liming Yang; Chun-Ang Lian; Spyros G. Pavlostathis; Zhiguang Qiu; Zhensheng Xiong; Yuanqi Liu; Bing Li; Jincheng Hu; Wenbo Fan; Xubiao Luo; Ke Yu (Environmental Research, 2024)

Assessment of benthic ecological status and heavy metal contamination in an estuarine intertidal mudflat in the Northern Bohai Sea - Ang Li; Jiaqi Li; Fang Liu; Ling Zhu; Lulei Liu; Suyan Xue; Meng Zhang; Yuze Tang; Yuze Mao (Marine Pollution Bulletin, 2024)

Path analysis of body weight and shell morphological traits in two Pacific abalone (Haliotis discus hannai) strains - Ang Li; Jiaqi Li; Lulei Liu; Suyan Xue; Ling Zhu; Yuze Mao (Aquaculture International, 2024)

Leaching behaviors of dissolved organic matter from face masks revealed by fluorescence EEM combined with FRI and PARAFAC - Zhong Jin; Weibo Zhang; Xihuan Wang; Ang Liu; Zhongyu Li; Yingchen Bai; Fengchang Wu (Water Research, 2024)

Quantitative prediction of surrounding rock deformation via an energy-based damage model combining with microseismic monitoring - Dingran Song; Yi Liu; Feng Dai; Ruochen Jiang; Ang Li (Tunnelling and Underground Space Technology, 2024)

Can xenobiotics support the growth of Mn(II)-oxidizing bacteria (MnOB)? A case of phenol-utilizing bacteria Pseudomonas sp. AN-1 - Aonan Qiao; Haixia Pan; Jiaxi Zang; Yiwen Zhang; Xianliang Yi; Yang Liu; Jingjing Zhan; Xiaojing Yang; Xu Zhao; Ang Li; Hao Zhou (Journal of Hazardous Materials, 2024)

Angiotoxic effects of chlorinated polyfluorinated ether sulfonate, a novel perfluorooctane sulfonate substitute, in vivo and in vitro - Zhenzhen Tan; Junli Lv; Haoran Li; Ziwen An; Longfei Li; Yijia Ke; Yi Liu; Xuehui Liu; Lei Wang; Ang Li; Huicai Guo (Journal of Hazardous Materials, 2024)

Innovative sodium acrylate wastewater resource recovery through electrodialysis with integrated bipolar membranes - Hailong Cui; Huimin Ruan; Haili Wei; Edison Huixiang Ang; Yudi Dong; Hao Lu; Hongyu Liu; Junbin Liao; Yanqing Xu; Jiangnan Shen (Journal of Environmental Chemical Engineering, 2024)

Development and evaluation of a haplotype reference panel of Zhikong scallop (Chlamys farreri) for genotype imputation - Mingyi Sui; Zhi Liu; Xiaowen Huang; Zujing Yang; Haitao Yu; Chang Cui; Yuqing Hu; Xuefeng Wang; Xiaojing Shen; Qianqian Mu; Mingxuan Teng; Ang Zhao; et al. (Aquaculture, 2024)

Mapping conservation priorities for wild yak (Bos mutus) habitats on the Tibetan Plateau, China - Hang Zhao; Nai'ang Wang; Hongyi Cheng; Yipeng Wang; Xiao Liu; Bin Qiao; Liqiang Zhao (Science of The Total Environment, 2024)

Physics-informed identification of marine vehicle dynamics using hydrodynamic dictionary library-inspired adaptive regression - Ang Liu; Yifan Xue; Hongde Qin; Zhongben Zhu (Ocean Engineering, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Biochar and microorganism assisted phytoremediation of severely molybdenum-contaminated soil: Efficacy, mechanisms and the impact of low temperatures - Chunyan Li; Jie Xing; Qian Xu; Di Cui; Yuqing Liu; Changlong Pang; Ang Li (Journal of Cleaner Production, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

First record of abnormal body coloration in a rockfish Sebastes koreanus (Scorpaenoidei: Sebastidae) from coastal water of China based on morphological characteristics and DNA barcoding - Ang Li; Huan Wang; Changting An; Shufang Liu (Journal of Oceanology and Limnology, 2024)

Spatiotemporal variations of parameters of internal solitary waves in the northern South China Sea - Yu’ang Liu; Yifei Jiang; Xiaojiang Zhang; Zhiyuan Wang; Yu Cao; Huizan Wang (Journal of Oceanology and Limnology, 2024)

Wollastonite powder application increases rice yield and CO2 sequestration in a paddy field in Northeast China - Fangna Wang; Feifei Zhu; Deze Liu; Yuying Qu; Dong Liu; Jin Xie; Ang Wang; Ronghua Kang; Zhi Quan; Yinghua Li; Xin Chen; Guochen Li; et al. (Plant and Soil, 2024)

An AI-powered approach to improving tunnel blast performance considering geological conditions - Yaosheng Liu; Ang Li; Feng Dai; Ruochen Jiang; Yi Liu; Rui Chen (Tunnelling and Underground Space Technology, 2024)

Early Paleozoic tectonic affinity of the Lesser Xing'an–Zhangguangcai Range, NE China: A continental arc along the western margin of the Jiamusi Block - Qingbin Guan; Boran Liu; Zhaoxu Chen; Yongjiang Liu; Sanzhong Li; Qi'ang Fang; Yujia Du (Lithos, 2024)

Influence of methane seep activities and sea-level changes on elemental and isotopic compositions and abundance of carbonates in sediments of the Okinawa Trough since the last glacial period - Qing Li; Hongbin Wang; Feng Cai; Di Luo; Fanxing Kong; Ang Li; Xiting Liu (Journal of Asian Earth Sciences, 2024)

Revolutionizing aqueous Zn-ion batteries: Precision control of H2O activity and Zn deposition through ammonium oxalate additive - Wenhao Ding; Guolang Zhou; Xiangjie Guo; Cheng Liu; Tianshi Wang; Yongsheng Fu; Jingzhou Yin; Lili Zhang; Edison Huixiang Ang (Chemical Engineering Journal, 2024)

Application of solid electrolytes in electrochemical reduction of CO2 or O2 - Jiayue Li; Zhuowen Wang; Sibei Liu; Zhonglin Chen; Jixian Yang; Zhiqiang Chen; Ang Li; Qinxue Wen; Li Wang; Shan Qiu; Chongwei Cui; Huiyuan Deng; et al. (Chemical Engineering Journal, 2024)

Deep learning to obtain high-throughput morphological phenotypes and its genetic correlation with swimming performance in juvenile large yellow croaker - Junjia Zeng; Miaosheng Feng; Yacheng Deng; Pengxin Jiang; Yinlin Bai; Jiaying Wang; Ang Qu; Wei Liu; Zhou Jiang; Qian He; Zhijun Wang; Peng Xu (Aquaculture, 2024)

Patterns and drivers of atmospheric inorganic nitrogen deposition in Northeast Asia - Abubakari Said Mgelwa; Feifei Zhu; Dan Huang; Linlin Song; Yingying Wang; Geshere Abdisa Gurmesa; Ang Wang; Miao Liu; Shaonan Huang; Qingyan Qiu; Hiroyuki Sase; Weixing Zhu; et al. (Journal of Environmental Management, 2024)

Hirsutinolide-type sesquiterpenoids with anti-prostate cancer activity from Cyanthillium cinereum - Song Ang; Chun Liu; Peng Hong; Lei Yang; Gui'e Hu; Xi Zheng; Jingwei Jin; Rihui Wu; Wing-Leung Wong; Kun Zhang; Lishe Gan; Dongli Li (Phytochemistry, 2023)

The cryptic step in the biogeochemical tellurium (Te) cycle: Indirect elementary Te oxidation mediated by manganese-oxidizing bacteria Bacillus sp. FF-1 - Yuqing Liu; Huiqing Ma; Ang Li; Haixia Pan; Xianliang Yi; Yang Liu; Jingjing Zhan; Hao Zhou (Environmental Research, 2023)

Effects of Environmental Heavy Metal Interactions on Renal Impairment: Epidemiological Evidence from Rural Northeastern China - Guohuan Yin; Xiaoyu Ge; Meiduo Zhao; Jing Xu; Ang Li; Yayuan Mei; Jingtao Wu; Xiaolin Liu; Lanping Wei; Qun Xu (Exposure and Health, 2023)

McPrA - A new gas profile inversion algorithm for MAX-DOAS and apply to 50 m vertical resolution - Jiangyi Zheng; Pinhua Xie; Xin Tian; Jin Xu; Ang Li; Bo Ren; Feng Hu; Zhaokun Hu; Yinsheng Lv; Zhidong Zhang; Wenqing Liu (Science of The Total Environment, 2023)

A novel 1T-2H MoS2/NaBi(MoO4)2 alternating-phase piezoelectric composites for high-efficient ultrasound-drived piezoelectric catalytic removal of Sildenafil - Qing-rui Zeng; Zi-ang Jia; Xu Liu; Jin-ping Cheng (Process Safety and Environmental Protection, 2023)

The effect of total alkalinity on growth performance and calcification in juvenile Pacific abalone Haliotis discus hannai - Meng Zhang; Jiaqi Li; Minghui Jiao; Yuze Tang; Ang Li; Lulei Liu; Longzhen Liu; Suyan Xue; Yuze Mao (Marine Environmental Research, 2023)

Multi-omics analyses reveal relationships among polyphenol-rich oolong tea consumption, gut microbiota, and metabolic profile: A pilot study - Ang Li; Ruixin Kou; Haiwei Liu; Mengshan Chen; Jin Wang; Qisijing Liu; Xiaolong Xing; Bowei Zhang; Lu Dong; Shuo Wang (Food Chemistry, 2023)

Study on the removal of iron (II) and manganese (II) in acidic mine drainage by red mud: Performance and mechanism - Ang Liu; Yingchen Bai; Chao Wang; Xianglong Lin; Fei Guo (Environmental Science and Pollution Research, 2023)

Generation estimation and metals recycling potentials evaluation of retired mobile phones in Korea - Ang Li; Bo Li; Huibin Wang; Xia Liu; Yanan Guo; Bin Lu (Environmental Science and Pollution Research, 2023)

Per- and polyfluoroalkyl substances and the associated thyroid cancer risk: A case-control study in China - Haoran Li; Ming Yang; Jing Yang; Samuel Seery; Chaoying Ma; Yi Liu; Xiaoguang Zhang; Ang Li; Huicai Guo (Chemosphere, 2023)

Performance enhancement of proton exchange membrane fuel cells with bio-inspired gear-shaped flow channels - Yuzhi Ke; Baotong Zhang; Wei Yuan; Yafeng Bai; Yonghao Zhao; Zi'ang Liu; Zhenhe Lin; Xinze Li; Yangang Wang; Yong Tang (Chemical Engineering Journal, 2023)

Carbon-based hierarchical porous structure accelerates heterogeneous nucleation of PEG molecules for solar/electro-driven thermal energy storage - Ruze Liu; Ang Li; Jinyan Liu; Wengeng Liu; Hao Zheng; Qingyang Du; Xiao Chen; Cheng Dong (Chemical Engineering Journal, 2023)

Assessment of germplasm resource and detection of genomic signature under artificial selection of Zhikong scallop (Chlamys farreri) - Xuefeng Wang; Zujing Yang; Liming Jiang; Zhi Liu; Xixi Dong; Mingyi Sui; Chenlin Yin; Xiaojing Shen; Ang Zhao; Jingjie Hu; Zhenmin Bao; Liping Hu; et al. (Aquaculture, 2023)

A glance of coupled water and wastewater treatment systems based on microbial fuel cells - Yulong Huang; Yaqian Zhao; Cheng Tang; Asheesh Kumar Yadav; Rouzbeh Abbassi; Peiying Kang; Yamei Cai; Ang Liu; Anran Yang; Min Li (Science of The Total Environment, 2023)

Measurement and modeling of water vapor sorption on nano-sized coal particulates and its implication on its transport and deposition in the environment - Sikandar Azam; Shimin Liu; Sekhar Bhattacharyya; Ang Liu (Science of The Total Environment, 2023)

The DYW domain of RARE1 plays an indispensable role in regulating accD-C794 RNA editing in Arabidopsis thaliana - Dan Liu; Zi-Ang Li; Yi Li; David P. Molloy; Chao Huang (Plant Science, 2023)

Removal of chloramphenicol and resistance gene changes in electric-integrated vertical flow constructed wetlands - Yuran Feng; Ailijiang Nuerla; Menghan Tian; Anwar Mamat; Ang Si; Jiali Chang; Mukadasi Abudureheman; Chaoyue He; Jinjin Zhu; Zhaohong Tong; Zhaojiang Liu (Journal of Environmental Management, 2023)

Solution-catalyzed carbothermal reduction of argo-waste SiO2 enables low-temperature and fast synthesis of Si(Ⅱ)-C anode - Zi'ang Liu; Ruohan Yu; Shaohua Zhu; Jiashen Meng; Xuanpeng Wang; Chaojiang Niu; Lianmeng Cui; Fan Qiao; Junjun Wang; Liqiang Mai (Chemical Engineering Journal, 2023)

Effect of slaughter age and postmortem aging time on tenderness and water-holding capacity of yak (Bos grunniens) longissimus thoracis muscle - Xueyuan Bai; Feng Yin; Ang Ru; Wei Tian; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Jiahui Li; Mancai Yin; Chaozhi Zhu; Gaiming Zhao (Meat Science, 2023)

Experimental and numerical tests on shear failure and size effect of CFRP-wrapped RC beams without stirrups: Influence of the shear-span ratio - Xuan'ang Jiang; Liu Jin; Kai Lu; Xiuli Du (Engineering Structures, 2023)

Boosting photocatalytic activity of CdLa2S4/ZnIn2S4 S-scheme heterojunctions with spatial separation of photoexcited carries - Meng Dai; Huijun Yu; Wenhan Chen; Kongyu-Ang Qu; Dong Zhai; Chengcheng Liu; Shan Zhao; Shuguang Wang; Zuoli He (Chemical Engineering Journal, 2023)

Correction to: Cucumis sativus PHLOEM PROTEIN 2-A1 like gene positively regulates salt stress tolerance in cucumber seedlings - Yuyang Si; Huaifu Fan; Hongjie Lu; Yapeng Li; Yuting Guo; Chen Liu; Li’ang Chai; Changxia Du (Plant Molecular Biology, 2023)

Neurotoxicological mechanisms of carbon quantum dots in a new animal model Dugesia japonica - Jing Kang; Qing Ai; Ang Zhao; Haijiao Wang; Xiangpeng Zhang; Yanli Liu; Lingke Zhang; Yuqing Liu (Ecotoxicology, 2023)

Dietary exposure to nTiO2 reduces byssus performance of mussels under ocean warming - Saishuai Li; Hui Chen; Chunhua Liu; Inna M. Sokolova; Yuchuan Chen; Fujing Deng; Zhe Xie; Li'ang Li; Wei Liu; James Kar-Hei Fang; Daohui Lin; Menghong Hu; et al. (Science of The Total Environment, 2023)

Investigation of dynamic crack formation mechanism based on a new crack dynamic driving model - Xiao Liu; Peng Yan; Wenbo Lu; Jin Zhu; Xiangyu Zhang; Ang Lu; Ming Chen; Gaohui Wang (Computers and Geotechnics, 2023)

Characterizing Anisotropic Swelling Strains of Coal Using Combined Rosette Strain Gauge and CT-Scans - Ang Liu; Shimin Liu; Kaiwen Xia; Peng Liu; Yun Yang; Gang Wang (Rock Mechanics and Rock Engineering, 2023)

Using DORIS data for validating real-time GNSS ionosphere maps - Ang Liu; Ningbo Wang; Denise Dettmering; Zishen Li; Michael Schmidt; Liang Wang; Hong Yuan (Advances in Space Research, 2023)

In situ reductive dehalogenation of groundwater driven by innovative organic carbon source materials: Insights into the organohalide-respiratory electron transport chain - Yang Yu; Yueyan Zhang; Yuqing Liu; Mengran Lv; Zeyi Wang; Li-lian Wen; Ang Li (Journal of Hazardous Materials, 2023)

Constructing functional thermal-insulation-layer on Co3O4 nanosphere for reinforced local-microenvironment photothermal PMS activation in pollutant degradation - Mengting Liu; Hongyang Zhu; Rongrong Du; Wuxiang Zhang; Weilong Shi; Zengjing Guo; Sheng Tang; Edison Huixiang Ang; Jun Yang; Jianming Pan; Fu Yang (Journal of Environmental Chemical Engineering, 2023)

Piezoelectric energy harvesting and dissipating behaviors of polymer-based piezoelectric composites for nanogenerators and dampers - Wenzheng Chen; Qitan Zheng; Yi Ang Lv; Yujie Chen; Qunfu Fan; Xunhuang Zhou; Hua Li; Qili Yu; Hezhou Liu (Chemical Engineering Journal, 2023)

Cyclical water vapor sorption-induced structural alterations of mine roof shale - Ang Liu; Shimin Liu; Rui Zhang; Guijie Sang; Kaiwen Xia (International Journal of Coal Geology, 2023)

Experimental and Numerical Studies on Bending and Failure Behaviour of Inflated Composite Fabric Membranes for Marine Applications - Yunling Ye; Jin Gan; Huabing Liu; Qingfei Guan; Zhongyi Zheng; Xiaolin Ran; Zi’ang Gao (Journal of Marine Science and Engineering, 2023)
Owing to their excellent physical characteristics of lightweightiness, compactness and rapid deployment, the inflated membrane structures satisfy the demands of maritime salvage and military transportation for long-distance delivery and rapid response. Exploring the failure behaviour of inflated membrane structures can greatly contribute to their widespread applications in ocean engineering. In this research, the main objective is to comprehensively investigate the bending and failure behaviour of inflated membrane structures. Thus, the Surface-Based Fluid Cavity method is employed to set up the finite element model (FEM) which is compared to the experimental results to verify its reliability. In parallel, the effects of internal pressure and wrinkles are discussed. An empirical expression of the ultimate bending loading was fitted by face-centred composite designs of the Response Surface Methodology. The results of experiments and FEM show that the bearing capacity of the inflated membrane structure is positively correlated with the internal pressure but decreased obviously with the occurrence and propagation of wrinkles. The deformation behaviour and the stress distribution are similar to those of the traditional four-point bending beam, and the local instability induced by wrinkles will cause structural failure. In addition, the numerical model and the proposed expression showed deviations below 5% in relation to the experimental measures. Therefore, the FEM and proposed expression are high of reliability and have important engineering guiding significance for the application of inflated membrane structures in ocean engineering.

Differential physiological response of marine and freshwater microalgae to polystyrene microplastics - Hengtao Xu; Li’ang Li; Youji Wang; Kecheng Qiu; Siyang Chen; Jiangning Zeng; Ruijuan Liu; Qikun Yang; Wei Huang (Journal of Hazardous Materials, 2023)

Integrated mRNA and miRNA expression analyses for Cryptocaryon irritans resistance in large yellow croaker (Larimichthys crocea) - Ang Qu; Yulin Bai; Jiaying Wang; Ji Zhao; Junjia Zeng; Yue Liu; Xintong Chen; Qiaozhen Ke; Pengxin Jiang; Xinyi Zhang; Xin Li; Peng Xu; et al. (Fish & Shellfish Immunology, 2023)

Cucumis sativus PHLOEM PROTEIN 2-A1 like gene positively regulates salt stress tolerance in cucumber seedlings - Yuyang Si; Huaifu Fan; Hongjie Lu; Yapeng Li; Yuting Guo; Chen Liu; Li’ang Chai; Changxia Du (Plant Molecular Biology, 2023)

scRNA-seq analysis reveals toxicity mechanisms in shrimp hemocytes subjected to nitrite stress - QingJian Liang; BeiBei Dong; Ang Li; LiTing Wu; Yu Zhang; Tao Han; Xing Liu (Chemosphere, 2023)

Characteristics and source analysis of polycyclic aromatic hydrocarbons in organisms and manure near Ardley Island, Antarctica - Bin Han; Gui Wang; Ang Liu; Yunchao Zheng; Li Zheng; Runtian Ding (Marine Pollution Bulletin, 2023)

Impacts of climate change and anthropogenic activities on the normalized difference vegetation index of desertified areas in northern China - Nan Meng; Nai’ang Wang; Hongyi Cheng; Xiao Liu; Zhenmin Niu (Journal of Geographical Sciences, 2023)

Comparison of alive and dead benthic foraminiferal fauna off the Changjiang Estuary: Understanding water-mass properties and taphonomic processes - Feng Jiang; Daidu Fan; Quanhong Zhao; Yijing Wu; Fahui Ren; Yan Liu; Ang Li (Frontiers in Marine Science, 2023)
Benthic foraminifera (BF) are utilized in palaeo-environmental reconstruction based on our understanding of how living individuals respond to environmental variations. However, there is still a lack of empirical insight into how non-environmental factors, such as taphonomic processes, influence the preservations of fossil BF in strata. In this study, we compare the spatial distribution and composition of alive and dead BF fauna in surface sediments to elucidate how well fossil foraminiferal fauna mirror quasi-contemporary alive BF groups indicative of different water masses off a mega-river (Changjiang) estuary, which is characterized by intense and complex river-sea interactions. On-site measurements of bottom water salinity, temperature, and dissolved oxygen were conducted in the summer to determine water mass properties. A same-site comparison of alive (Rose Bengal stained) and dead foraminiferal fauna in surface sediment samples over 73 stations was then carried out. Q-mode Hierarchical clustering analysis was used to differentiate foraminiferal assemblages based on the relative abundance of common species. Three distinct regions with different water-mass properties were identified. The distribution pattern of dead foraminiferal fauna is mainly inherited from alive fauna, while the density and diversity of the dead fauna were found to be higher than those of the alive one. Both alive and dead fauna were clustered into four assemblages. A few common alive species (small-agglutinated and thin-calcareous) were rarely found in dead fauna, and a few common dead species (preferring low temperature and indicating allochthonous sources) were rarely present in alive fauna. The alive foraminiferal abundance and diversity were mainly determined by food resources and environmental properties of salinity and temperature. Alive foraminiferal assemblages were separated by different water masses determined by river-sea interactions off the Changjiang Estuary. The “time-averaging” effect was found to be responsible for the higher density and diversity of the dead fauna. Disintegration of agglutinated tests, dissolution of calcareous tests and selective transportation were observed to contribute to the different species compositions between the alive and dead fauna. Nevertheless, indicative species-environment relations in alive and taphocoenose fauna were found to be almost homologous among most common species. This suggests that distinct benthic foraminiferal assemblages can be used to effectively differentiate between different water masses in the study coastal seas.

Dual RNA-seq reveals a host-pathogen interaction transcriptional regulation pattern between Cryptocaryon irritans and large yellow croaker (Larimichthys crocea) - Yulin Bai; Yue Liu; Ang Qu; Jiaying Wang; Ji Zhao; Qiaozhen Ke; Xintong Chen; Fei Pu; Linni Wu; Peng Xu; Tao Zhou (Aquaculture, 2023)

Deciphering the genetic basis and prediction genomic estimated breeding values of heat tolerance in Zhikong scallop Chlamys farreri - Haitao Yu; Mingyi Sui; Zujing Yang; Chang Cui; Xiujiang Hou; Zhi Liu; Xuefeng Wang; Xixi Dong; Ang Zhao; Yangfan Wang; Xiaoting Huang; Jingjie Hu; et al. (Aquaculture, 2023)

Maternal exposure to 4-vinylcyclohexene diepoxide during pregnancy induces subfertility and birth defects of offspring in mice - Wei Song; Ang Li; Qian-Qian Sha; Shao-Yuan Liu; Yong Zhou; Chang-Yin Zhou; Xue Zhang; Xiao-Zhen Li; Jia-Xin Jiang; Fei Li; Chao Li; Heide Schatten; et al. (Science of The Total Environment, 2023)

Spatiotemporal variations of precipitation concentration influenced by large-scale climatic factors and potential links to flood-drought events across China 1958–2019 - Sijia Fu; Huilan Zhang; Qiang Zhong; Qigang Chen; Ang Liu; Jun Yang; Jianzhuang Pang (Atmospheric Research, 2023)

Identification and Expression Analysis of LncRNAs Reveal the Immune Mechanism of Visceral White-Nodules Disease Resistance in Large Yellow Croaker - Yulin Bai; Xintong Chen; Ang Qu; Yue Liu; Ji Zhao; Qiaozhen Ke; Fei Pu; Linni Wu; Hongshu Chi; Hui Gong; Tao Zhou; Peng Xu (Marine Biotechnology, 2023)

Ionic liquid etched and microwave-assisted delaminated MXene as an excellent electrocatalyst for the hysteretic negative reaction of vanadium redox flow batteries - Minghua Jing; Xi Li; Hao Yu; Xinyu An; Zhuling Liu; Ang Zhang; Xindong Qin; Chao Li; Dawei Fang (Chemical Engineering Journal, 2023)

SHAKING: Adjusted spherical harmonics adding KrigING method for near real-time ionospheric modeling with multi-GNSS observations - Ang Liu; Zishen Li; Ningbo Wang; Yan Zhang; Andrzej Krankowski; Hong Yuan (Advances in Space Research, 2023)

The Combination of Platelet Rich Plasma Gel, Human Umbilical Mesenchymal Stem Cells and Nanohydroxyapatite/polyamide 66 Promotes Angiogenesis and Bone Regeneration in Large Bone Defect - Wei Liu; Yong Huang; Daqian Liu; Teng Zeng; Jingzhe Wang; Ang Li; Dawei Wang; Xiaoyu Wang (Tissue Engineering and Regenerative Medicine, 2022)

Determination of Mechanical Property Evolutions of Shales by Nanoindentation and High-Pressure CO2 and Water Treatments: A Nano-to-Micron Scale Experimental Study - Yiwei Liu; Shimin Liu; Ang Liu; Yong Kang (Rock Mechanics and Rock Engineering, 2022)

The Landscape of DNA Methylation Generates Insight Into Epigenetic Regulation of Differences Between Slow-Twitch and Fast-Twitch Muscles in Pseudocaranx dentex - Busu Li; Huan Wang; Ang Li; Changting An; Ling Zhu; Shufang Liu; Zhimeng Zhuang (Frontiers in Marine Science, 2022)
Skeletal muscles of teleost are mainly composed of slow-twitch muscles (SM) and fast-twitch muscles (FM) differed in contractile properties, metabolic capacities, and regeneration rate. The transcriptional regulatory mechanisms that control different muscle types have been elucidated in teleost according to transcriptome between SM and FM. However, the differences between SM and FM were affected not only by genotype but also by complicated epigenetic effects, including DNA methylation, which usually regulates genes in transcription level. To determine the essential role of DNA methylation in the regulation of different muscle types, we analyzed whole-genome methylation profiles of pelagic migratory fish Pseudocaranx dentex with abundant and well-separated SM and integrated DNA methylation profiles with the previously obtained transcriptome data. A total of 4,217 differentially methylated genes (DMGs) were identified, of which 3,582 were located in the gene body and 635 in the promoter. These DMGs mainly participated in muscle metabolite and cell junction. Enriched cell junction pathway reflected different capillary distribution between SM and FM. Through comprehensive analysis of methylome and transcriptome, 84 differentially expressed genes (DEGs) showed significant methylation variation in promoters between SM and FM, indicating that their expression was regulated by DNA methylation. Hypomethylated and highly expressed oxygen storage protein Myoglobin ( myg ) in SM indicated demethylation of myg promoter could upregulate its expression, thus increasing O 2 supplying and meeting oxygen demands of SM. Hypermethylated and lowly expressed tnn (Troponin) and rlc (myosin regulatory light chain) in SM may be associated with low mobility of myosin cross bridges, which lead to slower and less frequent muscle contraction in SM than in FM. In addition, hypomethylated and highly expressed lbx1 (Ladybird homeobox protein homolog 1) and epo (erythropoietin) may be related to increased satellite cell numbers, and Semaphorin/Plexin genes may be related to higher rate of neuromuscular connection reconstruction, which further promote high muscle regeneration efficiency in SM. Our study elucidated the potential DNA methylation mechanisms that regulate physiological characteristics differences between SM and FM, which could facilitate our understanding of skeletal muscle adaptation in pelagic migratory fishes and further enrich the theoretical basis for the study of physiological characteristics and adaptive evolution in teleost fishes.

Roles of neutrophil reactive oxygen species (ROS) generation in organ function impairment in sepsis - Jiaqi Lu; Jingyuan Liu; Ang Li (Journal of Zhejiang University-SCIENCE B, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Genome-wide CRISPR activation screen identifies candidate receptors for SARS-CoV-2 entry - Shiyou Zhu; Ying Liu; Zhuo Zhou; Zhiying Zhang; Xia Xiao; Zhiheng Liu; Ang Chen; Xiaojing Dong; Feng Tian; Shihua Chen; Yiyuan Xu; Chunhui Wang; et al. (Science China Life Sciences, 2022)

The association between urine elements and fasting glucose levels in a community-based elderly people in Beijing - Liu Liu; Ang Li; Qun Xu; Qin Wang; Feng Han; Chunyu Xu; Zhe Liu; Dongqun Xu; Donggang Xu (Environmental Science and Pollution Research, 2022)

Biodiversity and degradation potential of oil-degrading bacteria isolated from sediments of hydrothermal and non-hydrothermal areas of the Southwest Mid-Indian Ocean Ridge - Haolei Shi; Jiangfeng Cheng; Wei Gao; Meng Ma; Ang Liu; Tianyi Hu; Bin Han; Li Zheng (Environmental Science and Pollution Research, 2022)

Improved Agrobacterium tumefaciens-mediated transformation using antibiotics and acetosyringone selection in cucumber - Changxia Du; Li’ang Chai; Chen Liu; Yuyang Si; Huaifu Fan (Plant Biotechnology Reports, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

A satellite-based method for modeling ionospheric slant TEC from GNSS observations: algorithm and validation - Wen Li; Zishen Li; Ningbo Wang; Ang Liu; Kai Zhou; Hong Yuan; Andrzej Krankowski (GPS Solutions, 2022)
Total Electron Content (TEC) modeling is critical for Global Navigation Satellite System (GNSS) users to mitigate ionospheric delay errors. The mapping function is usually used for Vertical TEC ionospheric correction models for slant and vertical TEC conversion. But the mapping function cannot characterize TEC variation in different azimuths between the user and satellites. The ionospheric modeling error resulting from the mapping function tends to be bigger in middle and low latitudes. Therefore, a new algorithm for ionospheric Slant TEC (STEC) modeling with Satellite-based Ionospheric Model (SIM) is proposed in this contribution. Validation tests are carried out with GNSS observation data from the Crustal Movement Observation Network of China during different solar activities and in different seasons. The performance of SIM is compared with that of several commonly-used Global Ionospheric Map (GIM) and Regional Ionospheric Map (RIM) products. The results show that the STEC bias and STD of SIM are within 1.0 TECU and about 2.0 TECU, respectively, and SIM can correct over 90% STEC RMS errors, outperforming the GIM and RIM products. Consequently, the SIM algorithm can be a new option for high-accuracy ionospheric delay correction in regional and local GNSS networks.

FOXA2 inhibits doxorubicin-induced apoptosis via transcriptionally activating HBP rate-limiting enzyme GFPT1 in HCC cells - Huang Huang; Yuhan Wang; Tianmiao Huang; Lingyan Wang; Yangzhi Liu; Qiong Wu; Ang Yu; Meiyun Shi; Xiaoyu Wang; Wenli Li; Jianing Zhang; Yubo Liu (Journal of Physiology and Biochemistry, 2021)

A New Scheme of Adaptive Covariance Inflation for Ensemble Filtering Data Assimilation - Ang Su; Liang Zhang; Xuefeng Zhang; Shaoqing Zhang; Zhao Liu; Caili Liu; Anmin Zhang (Journal of Marine Science and Engineering, 2021)
Due to the model and sampling errors of the finite ensemble, the background ensemble spread becomes small and the error covariance is underestimated during filtering for data assimilation. Because of the constraint of computational resources, it is difficult to use a large ensemble size to reduce sampling errors in high-dimensional real atmospheric and ocean models. Here, based on Bayesian theory, we explore a new spatially and temporally varying adaptive covariance inflation algorithm. To increase the statistical presentation of a finite background ensemble, the prior probability of inflation obeys the inverse chi-square distribution, and the likelihood function obeys the t distribution, which are used to obtain prior or posterior covariance inflation schemes. Different ensemble sizes are used to compare the assimilation quality with other inflation schemes within both the perfect and biased model frameworks. With two simple coupled models, we examined the performance of the new scheme. The results show that the new inflation scheme performed better than existing schemes in some cases, with more stability and fewer assimilation errors, especially when a small ensemble size was used in the biased model. Due to better computing performance and relaxed demand for computational resources, the new scheme has more potential applications in more comprehensive models for prediction initialization and reanalysis. In a word, the new inflation scheme performs well for a small ensemble size, and it may be more suitable for large-scale models.

Influences of Loading Method and Notch Type on Rock Fracture Toughness Measurements: From the Perspectives of T-Stress and Fracture Process Zone - Mingdong Wei; Feng Dai; Yi Liu; Ang Li; Zelin Yan (Rock Mechanics and Rock Engineering, 2021)

Quantifying and Modeling of In Situ Stress Evolutions of Coal Reservoirs for Helium, Methane, Nitrogen and CO2 Depletions - Xiaowei Hou; Shimin Liu; Guofu Li; Yanming Zhu; Ang Liu (Rock Mechanics and Rock Engineering, 2021)

Phylogenomic Analyses of a Clade Within the Family Flavobacteriaceae Suggest Taxonomic Reassignments of Species of the Genera Algibacter, Hyunsoonleella, Jejuia, and Flavivirga, and the Proposal of Pseudalgibacter gen. nov. and Pseudalgibacter alginicilyticus comb. nov. - Miao Li; Ling-Zhi Hou; Xing-Hao Xu; Xiao-Xiao Wang; Ming-Can Zheng; Yan-Jiao Zhang; Ang Liu (Current Microbiology, 2021)

Swi6B , an alternative splicing isoform of Swi6, mediates the cell wall integrity of Ganoderma lucidum - Lingdan Lian; Guang Zhang; Jing Zhu; Yunxiao Wang; Lingshuai Wang; Rui Liu; Liang Shi; Ang Ren; Mingwen Zhao (Environmental Microbiology, 2021)
Summary The cell wall integrity (CWI) signaling activates the transcription factor Swi6 through a MAPK signaling cascade in response to cell wall stresses. In this study, we observed two different mRNA variants of swi6 ( GlSwi6A and GlSwi6B ) existed, due to alternative splicing. Besides, the expression level of GlSwi6B was higher than that of the GlSwi6A mRNA variant. The co‐silencing of GlSwi6A and GlSwi6B was more sensitive to cell wall stress compared with WT, resulting in a decrease of 78% and 76% in chitin and β‐1,3‐ d ‐glucan content respectively. However, only the overexpression of GlSwi6B decreased the sensitivity to cell wall stress and increased the content of chitin and β‐1,3‐ d ‐glucan compared with the WT strain. Furthermore, Y1H, EMSA and BLI assays revealed that the GlSwi6B could bind to the promoters of chitin and glucan synthesis genes (GL24454 and GL18134). However, the binding phenome has not been observed in the isoform GlSwi6A. Taken together, our results found two different transcripts generated from Swi6 , in which the alternative splice isoform of GlSwi6B participates in regulating the CWI of G . lucidum . This study provides the first insight into the alternative splicing isoform of GlSwi6B in the regulation of CWI signaling in fungi.

Numerical Analysis of the Water-blocking Performance of a Floor with a Composite Structure under Fluid–solid Coupling - Ang Li; Qian Mu; Li Ma; Chaoyang Liu; Shengquan Wang; Feng Wang; Lin Mou (Mine Water and the Environment, 2021)

Distribution, sources, and risk assessment of polycyclic aromatic hydrocarbons (PAHs) in surface sediments from Daya Bay, South China - Bin Han; Dongyang Cui; Ang Liu; Qian Li; Li Zheng (Environmental Science and Pollution Research, 2021)

Frequency Characteristics of Acoustic Emissions Induced by Crack Propagation in Rock Tensile Fracture - Ruochen Jiang; Feng Dai; Yi Liu; Ang Li; Peng Feng (Rock Mechanics and Rock Engineering, 2021)

Reclassification of Algibacter wandonensis as a Later Heterotypic Synonym of Algibacter lectus Based on Whole-Genome Sequence Analysis - Ang Liu; Hui Wang; Yuan-Yuan Yang; Qing-Jie Xue; Xiu-Zhen Li (Current Microbiology, 2021)

Changes in arthropod community but not plant quality benefit a specialist herbivore on plants under reduced water availability - Po-An Lin; Chia-Ming Liu; Jia-Ang Ou; Cheng-Han Sun; Wen-Po Chuang; Chuan-Kai Ho; Natsuko Kinoshita; Gary W. Felton (Oecologia, 2021)

Zongyanglinia huanghaiensis gen. nov., sp. nov., a novel denitrifying bacterium isolated from the yellow sea, and transfer of Pelagicola marinus to Zongyanglinia gen. nov. as Zongyanglinia marinus comb. nov - Lili Xu; Ang Liu; Yan-Jiao Zhang (Antonie van Leeuwenhoek, 2021)

Nitric oxide regulates ganoderic acid biosynthesis by the S‐nitrosylation of aconitase under heat stress in Ganoderma lucidum - Rui Liu; Ting Zhu; Tao Yang; Zhengyan Yang; Ang Ren; Liang Shi; Jing Zhu; Hanshou Yu; Mingwen Zhao (Environmental Microbiology, 2021)
Summary Nitric oxide (NO) is an important signalling molecule in stress response of organisms. We previously reported that NO decreases heat stress (HS)‐induced ganoderic acid (GA) accumulation in Ganoderma lucidum . To explore the mechanisms by which NO modulates GA biosynthesis under HS, the effect of NO on the reactive oxygen species (ROS) content was examined. The results showed that NO decreased the production of mitochondrial ROS (mitROS) by 60% under HS. Further research revealed that NO reduced the mitROS content by inhibiting aconitase (Acon) activity. The GA content in Acon‐silenced (Aconi) strains treated with NO donor did not differ significantly from that in untreated Aconi strains. To study the mechanism by which Acon activity is inhibited, the S‐nitrosylation level of Acon was determined. Biotin‐switch technology and mass spectrometry analysis were used to show that Acon is S‐nitrosylated at the Cys‐594 amino acid residue. Substitution of Cys‐594 with a Ser, which cannot be S‐nitrosylated, abolished the responsiveness of Acon to the NO‐induced reduction in its enzymatic activity. These findings demonstrate that NO inhibits Acon activity through S‐nitrosylation at Cys‐594. In summary, these findings describe mechanism by which NO regulates GA biosynthesis via S‐nitrosylation of Acon under HS condition in G . lucidum .

The Application of Decellularized Adipose Tissue Promotes Wound Healing - Zenan Xia; Xiao Guo; Nanze Yu; Ang Zeng; Loubin Si; Fei Long; Wenchao Zhang; Xiaojun Wang; Lin Zhu; Zhifei Liu (Tissue Engineering and Regenerative Medicine, 2020)

Continuous Compaction and Permeability Evolution in Longwall Gob Materials - Ang Liu; Shimin Liu; Gang Wang; Derek Elsworth (Rock Mechanics and Rock Engineering, 2020)

Modeling of Coal Matrix Apparent Strains for Sorbing Gases Using a Transversely Isotropic Approach - Ang Liu; Shimin Liu; Gang Wang; Guijie Sang (Rock Mechanics and Rock Engineering, 2020)

OP16 induces deadly autophagy and apoptosis of cells by inhibiting Akt in esophageal squamous cell carcinoma - Guiqin Hou; Ang Jia; Li Yang; Yu Zhao; Yi Hu; Wuduo Zhao; Wen Zhao; Hong-Min Liu; Zhaoming Lu (Molecular and Cellular Biochemistry, 2020)

Whole genome analysis calls for a taxonomic rearrangement of the genus Colwellia - Ang Liu; Yan-Jiao Zhang; Peng Cheng; Ya-Jie Peng; Jochen Blom; Qing-Jie Xue (Antonie van Leeuwenhoek, 2020)

Effects of osmotic stress on the expression profiling of aquaporin genes in the roughskin sculpin (Trachidermus fasciatus) - Qian Ma; Xinfu Liu; Ang Li; Shufang Liu; Zhimeng Zhuang (Acta Oceanologica Sinica, 2020)

Colletotrichum fructicola STE50 is required for vegetative growth, asexual reproduction, appressorium formation, pathogenicity and the response to external stress - Yan-ying Chen; Jun-ang Liu; Shi-qiang Jiang; He Li; Guo-ying Zhou (Journal of Plant Pathology, 2020)

Oxidation Modification of Polyacrylonitrile-Based Carbon Fiber and Its Electro-Chemical Performance as Marine Electrode for Electric Field Test - Xuerong Zai; Ang Liu; Yuhua Tian; Fanggang Chai; Yubin Fu (Journal of Ocean University of China, 2020)

Litorilituus lipolyticus sp. nov., isolated from intertidal sand of the Yellow Sea in China, and emended description of Colwellia asteriadis - Ang Liu; Yan-Jiao Zhang; Qing-Jie Xue; Hui Wang; Yuan-Yuan Yang; Feng Du; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2020)

IGS real-time service for global ionospheric total electron content modeling - Zishen Li; Ningbo Wang; Manuel Hernández-Pajares; Yunbin Yuan; Andrzej Krankowski; Ang Liu; Jiuping Zha; Alberto García-Rigo; David Roma-Dollase; Heng Yang; Denis Laurichesse; Alexis Blot (Journal of Geodesy, 2020)

Investigation of the Long-Term Strength Properties of a Discontinuity by Shear Relaxation Tests - Ang Liu; Wenli Lin; Jingcai Jiang (Rock Mechanics and Rock Engineering, 2020)

Effects of osmotic stress on Na+/K+-ATPase, caspase 3/7 activity, and the expression profiling of sirt1, hsf1, and hsp70 in the roughskin sculpin (Trachidermus fasciatus) - Qian Ma; JieHua Kuang; Xinfu Liu; Ang Li; Wenrong Feng; Zhimeng Zhuang (Fish Physiology and Biochemistry, 2020)

Inversion of Evaporation and Water Vapor Transport Using HY-2 Multi-Sensor Data - Dong’ang Liu; Jian Sun; Changlong Guan (Journal of Ocean University of China, 2020)

Identification of the magnesium transport (MGT) family in Poncirus trifoliata and functional characterization of PtrMGT5 in magnesium deficiency stress - Xiao Liu; Ling-Xia Guo; Li-Juan Luo; Yong-Zhong Liu; Shu-Ang Peng (Plant Molecular Biology, 2019)

Flavivirga rizhaonensis sp. nov., a marine bacterium isolated from intertidal sand - Ang Liu; Hong-Mei Liu; Feng Du; Shuang Wang; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Qing-Jie Xue; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2019)

Regional ionospheric TEC modeling based on a two-layer spherical harmonic approximation for real-time single-frequency PPP - Zishen Li; Ningbo Wang; Liang Wang; Ang Liu; Hong Yuan; Kefei Zhang (Journal of Geodesy, 2019)

Proteomics analysis of Schwann cell-derived exosomes: a novel therapeutic strategy for central nervous system injury - Zhijian Wei; Baoyou Fan; Han Ding; Yang Liu; Haoshuai Tang; Dayu Pan; Jiaxiao Shi; Pengyuan Zheng; Hongyu Shi; Heng Wu; Ang Li; Shiqing Feng (Molecular and Cellular Biochemistry, 2019)

Exploring Local Perceptions of and Attitudes toward Endangered François’ Langurs (Trachypithecus francoisi) in a Human-Modified Habitat - Kefeng Niu; Wei Liu; Zhi Xiao; Ankang Wu; Tianyou Yang; Isidoro Riondato; Amanda L. Ellwanger; Andie Ang; Marco Gamba; Yeqin Yang; Cristina Giacoma (International Journal of Primatology, 2019)

Disruption of bone morphogenetic protein type IA receptor in osteoblasts impairs bone quality and bone strength in mice - Quanwei Bao; Ang Li; Sixu Chen; Jianquan Feng; Huayu Liu; Hao Qin; Junfeng Li; Daocheng Liu; Yue Shen; Zhaowen Zong (Cell and Tissue Research, 2018)

The roles of the COX2/PGE2/EP axis in therapeutic resistance - Dali Tong; Qiuli Liu; Lin-ang Wang; Qiubo Xie; Jian Pang; Yiqiang Huang; Luofu Wang; Gaolei Liu; Dianzheng Zhang; Weihua Lan; Jun Jiang (Cancer and Metastasis Reviews, 2018)

Relative Permeability of Gas for Unconventional Reservoirs - Ang Liu; Kai Wang; Jie Zang; Feng Du; Aitao Zhou (Transport in Porous Media, 2018)

Conversion of phosphatidylinositol (PI) to PI4‐phosphate (PI4P) and then to PI(4,5)P 2 is essential for the cytosolic Ca 2+ concentration under heat stress in Ganoderma lucidum - Yong‐Nan Liu; Xiao‐Xiao Lu; Ang Ren; Liang Shi; Jing Zhu; Ai‐Liang Jiang; Han‐Shou Yu; Ming‐Wen Zhao (Environmental Microbiology, 2018)
Summary How cells drive the phospholipid signal response to heat stress (HS) to maintain cellular homeostasis is a fundamental issue in biology, but the regulatory mechanism of this fundamental process is unclear. Previous quantitative analyses of lipids showed that phosphatidylinositol (PI) accumulates after HS in Ganoderma lucidum , implying the inositol phospholipid signal may be associated with HS signal transduction. Here, we found that the PI‐4‐kinase and PI‐4‐phosphate‐5‐kinase activities are activated and that their lipid products PI‐4‐phosphate and PI‐4,5‐bisphosphate are increased under HS. Further experimental results showed that the cytosolic Ca 2+ ([Ca 2+ ] c ) and ganoderic acid (GA) contents induced by HS were decreased when cells were pretreated with Li + , an inhibitor of inositol monophosphatase, and this decrease could be rescued by PI and PI‐4‐phosphate. Furthermore, inhibition of PI‐4‐kinases resulted in a decrease in the Ca 2+ and GA contents under HS that could be rescued by PI‐4‐phosphate but not PI. However, the decrease in the Ca 2+ and GA contents by silencing of PI‐4‐phosphate‐5‐kinase could not be rescued by PI‐4‐phosphate. Taken together, our study reveals the essential role of the step converting PI to PI‐4‐phosphate and then to PI‐4,5‐bisphosphate in [Ca 2+ ] c signalling and GA biosynthesis under HS.

Long-term study on seasonal changes in floristic composition and structure of marine macroalgal communities along the coast of Northern Taiwan, southern East China Sea - Showe-Mei Lin; Li-Chun Tseng; Put O. Ang; John Bolton; Li-Chia Liu (Marine Biology, 2018)

Over-expression of the Arabidopsis formate dehydrogenase in chloroplasts enhances formaldehyde uptake and metabolism in transgenic tobacco leaves - Ru Wang; Zhidong Zeng; Hongxia Guo; Hao Tan; Ang Liu; Yan Zhao; Limei Chen (Planta, 2018)

Erratum to: Forskolin Induces Hyperphosphorylation of Tau Accompanied by Cell Cycle Reactivation in Primary Hippocampal Neurons - Hai-Hong Wang; Yan Li; Ang Li; Fang Yan; Zhen-Lin Li; Zhong-Ying Liu; Lei Zhang; Jian Zhang; Wei-Ren Dong; Lin Zhang (Molecular Neurobiology, 2018)

Forskolin Induces Hyperphosphorylation of Tau Accompanied by Cell Cycle Reactivation in Primary Hippocampal Neurons - Hai-Hong Wang; Yan Li; Ang Li; Fang Yan; Zhen-Lin Li; Zhong-Ying Liu; Lei Zhang; Jian Zhang; Wei-Ren Dong; Lin Zhang (Molecular Neurobiology, 2018)

Phospholipase D and phosphatidic acid mediate heat stress induced secondary metabolism in Ganoderma lucidum - Yong‐Nan Liu; Xiao‐Xiao Lu; Dai Chen; Ya‐Ping Lu; Ang Ren; Liang Shi; Jing Zhu; Ai‐Liang Jiang; Han‐Shou Yu; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Phospholipid‐mediated signal transduction plays a key role in responses to environmental changes, but little is known about the role of phospholipid signalling in microorganisms. Heat stress (HS) is one of the most important environmental factors. Our previous study found that HS could induce the biosynthesis of the secondary metabolites, ganoderic acids (GA). Here, we performed a comprehensive mass spectrometry‐based analysis to investigate HS‐induced lipid remodelling in Ganoderma lucidum . In particular, we observed a significant accumulation of phosphatidic acid (PA) on HS. Further genetic tests in which pld ‐silencing strains were constructed demonstrated that the accumulation of PA is dependent on HS‐activated phospholipase D (PLD) hydrolysing phosphatidylethanolamine. Furthermore, we determined the role of PLD and PA in HS‐induced secondary metabolism in G . lucidum . Exogenous 1‐butanol, which decreased PLD‐mediated formation of PA, reverses the increased GA biosynthesis that was elicited by HS. The pld ‐silenced strains partly blocked HS‐induced GA biosynthesis, and this block can be reversed by adding PA. Taken together, our results suggest that PLD and PA are involved in the regulation of HS‐induced secondary metabolism in G . lucidum . Our findings provide key insights into how microorganisms respond to heat stress and then consequently accumulate secondary metabolites by phospholipid remodelling.

Physiological and transcriptional analysis reveals pathways involved in iron deficiency chlorosis in fragrant citrus - Long-Fei Jin; Yong-Zhong Liu; Wei Du; Li-Na Fu; Syed Bilal Hussain; Shu-Ang Peng (Tree Genetics & Genomes, 2017)

Safety, pharmacokinetics, and pharmacodynamics of BMS-986142, a novel reversible BTK inhibitor, in healthy participants - Sun Ku Lee; Jun Xing; Ian M. Catlett; Robert Adamczyk; Amber Griffies; Ang Liu; Bindu Murthy; Miroslawa Nowak (European Journal of Clinical Pharmacology, 2017)

Membrane fluidity is involved in the regulation of heat stress induced secondary metabolism in Ganoderma lucidum - Yong‐Nan Liu; Tian‐Jun Zhang; Xiao‐Xiao Lu; Bao‐Liang Ma; Ang Ren; Liang Shi; Ai‐Liang Jiang; Han‐Shou Yu; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum has become a potential model system for evaluating how environmental factors regulate the secondary metabolism of basidiomycetes. Heat stress (HS) is one of the most important environmental factors. It was previously reported that HS could induce the biosynthesis of ganoderic acids (GA). In this study, we found that HS increased GA biosynthesis and also significantly increased cell membrane fluidity. Furthermore, our results showed that addition of the membrane rigidifier dimethylsulfoxide (DMSO) could revert the increased GA biosynthesis elicited by HS. These results indicate that an increase in membrane fluidity is associated with HS‐induced GA biosynthesis. Further evidence showed that the GA content was decreased in D9des ‐silenced strains and could be reverted to WT levels by addition of the membrane fluidizer benzyl alcohol (BA). In contrast, GA content was increased in D9des ‐overexpression strains and could be reverted to WT levels by the addition of DMSO. Furthermore, both membrane fluidity and GA biosynthesis induced by HS could be reverted by DMSO in WT and D9des ‐silenced strains. To the best of our knowledge, this is the first report demonstrating that membrane fluidity is involved in the regulation of heat stress induced secondary metabolism in filamentous fungi.

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Identification and transcript profiles of citrus growth-regulating factor genes involved in the regulation of leaf and fruit development - Xiao Liu; Ling-Xia Guo; Long-Fei Jin; Yong-Zhong Liu; Tao Liu; Yu-Hua Fan; Shu-Ang Peng (Molecular Biology Reports, 2016)

Prescreening, identification and harvesting of microalgae with antibacterial activity - Ang Li; Ling Zhang; Zhen-yu Zhao; Sha-sha Ma; Meng Wang; Ping-huai Liu (Biologia, 2016)

The Role of Cdk5 in Alzheimer’s Disease - Shu-Lei Liu; Chong Wang; Teng Jiang; Lan Tan; Ang Xing; Jin-Tai Yu (Molecular Neurobiology, 2016)

Overexpression of Aiolos in Peripheral Blood Mononuclear Cell Subsets from Patients with Systemic Lupus Erythematosus and Rheumatoid Arthritis - Xinze Cai; Xudong Liu; Shuyan Du; Xiaoxue Xu; Ang Liu; Xin Ge; Ying Qiao; Yi Jiang (Biochemical Genetics, 2016)

Transcript analysis of citrus miRNA397 and its target LAC7 reveals a possible role in response to boron toxicity - Long-Fei Jin; Yong-Zhong Liu; Xin-Xing Yin; Shu-Ang Peng (Acta Physiologiae Plantarum, 2016)

Citrus sucrose transporter genes: genome-wide identification and transcript analysis in ripening and ABA-injected fruits - Mohammad Zahidul Islam; Long-Fei Jin; Cai-Yun Shi; Yong-Zhong Liu; Shu-Ang Peng (Tree Genetics & Genomes, 2015)

The bacterial lipopeptide iturins induce V erticillium dahliae cell death by affecting fungal signalling pathways and mediate plant defence responses involved in pathogen‐associated molecular pattern‐triggered immunity - Qin Han; Fengli Wu; Xiaonan Wang; Hong Qi; Liang Shi; Ang Ren; Qinghai Liu; Mingwen Zhao; Canming Tang (Environmental Microbiology, 2015)
Summary V erticillium wilt in cotton caused by V erticillium dahliae is one of the most serious plant diseases worldwide. Because no known fungicides or cotton cultivars provide sufficient protection against this pathogen, V . dahliae causes major crop yield losses. Here, an isolated cotton endophytic bacterium, designated B acillus amyloliquefaciens 41 B ‐1, exhibited greater than 50% biocontrol efficacy against V . dahliae in cotton plants under greenhouse conditions. Through high‐performance liquid chromatography and mass analysis of the filtrate, we found that the antifungal compounds present in the strain 41 B ‐1 culture filtrate were a series of isoforms of iturins. The purified iturins suppressed V . dahliae microsclerotial germination in the absence or presence of cotton. Treatment with the iturins induced reactive oxygen species bursts, H og1 mitogen‐activated protein kinase (MAPK) activation and defects in cell wall integrity. The oxidative stress response and high‐osmolarity glycerol pathway contribute to iturins resistance in V . dahliae . In contrast, the S lt2 MAPK pathway may be involved in iturins sensitivity in this fungus. In addition to antagonism, iturins could induce plant defence responses as activators and mediate pathogen‐associated molecular pattern‐triggered immunity. These findings suggest that iturins may affect fungal signalling pathways and mediate plant defence responses against V . dahliae .

Genome-wide identification of citrus ATP-citrate lyase genes and their transcript analysis in fruits reveals their possible role in citrate utilization - Xiao-Mei Hu; Cai-Yun Shi; Xiao Liu; Long-Fei Jin; Yong-Zhong Liu; Shu-Ang Peng (Molecular Genetics and Genomics, 2015)

Differences in boron distribution and forms in four citrus scion–rootstock combinations with contrasting boron efficiency under boron-deficient conditions - Nannan Wang; Tingshuai Yan; Lina Fu; Gaofeng Zhou; Yongzhong Liu; Shu’ang Peng (Trees, 2014)

Identification and transcript analysis of two glutamate decarboxylase genes, CsGAD1 and CsGAD2, reveal the strong relationship between CsGAD1 and citrate utilization in citrus fruit - Xiao Liu; Xiao-Mei Hu; Long-Fei Jin; Cai-Yun Shi; Yong-Zhong Liu; Shu-Ang Peng (Molecular Biology Reports, 2014)

Overexpression of CsCLCc, a Chloride Channel Gene from Poncirus trifoliata, Enhances Salt Tolerance in Arabidopsis - Qingjiang Wei; Yongzhong Liu; Gaofeng Zhou; Qiaohong Li; Chengquan Yang; Shu-ang Peng (Plant Molecular Biology Reporter, 2013)

Isolation and characterization of polymorphic microsatellite markers in the fish Garra orientalis (oriental sucking barb) - Li-Wei Su; Zhi-Zhi Liu; Cong-Tao Wang; Zhen Zeng; Ang-Yu Liu; Wen-Qiao Tang; Jin-Quan Yang (Conservation Genetics Resources, 2013)

Effects of Selenium Source and Level on Growth Performance, Tissue Selenium Concentrations, Antioxidation, and Immune Functions of Heat-Stressed Broilers - Xiudong Liao; Lin Lu; Sufen Li; Songbai Liu; Liyang Zhang; Guangying Wang; Ang Li; Xugang Luo (Biological Trace Element Research, 2012)

Reservoir information extraction using a fractional fourier transform and a smooth pseudo Wigner-Ville distribution - Zhu-Wen Wang; Xiao-Li Wang; Min Xiang; Jing-Hua Liu; Xue-Ang Zhang; Chuang Yang (Applied Geophysics, 2012)

Boron distribution and mobility in navel orange grafted on citrange and trifoliate orange - Gui-Dong Liu; Rui-Dong Wang; Li-Shu Wu; Shu-Ang Peng; Yun-Hua Wang; Cun-Cang Jiang (Plant and Soil, 2012)

Seismic fragility analysis of highway bridges considering multi-dimensional performance limit state - Qi’ang Wang; Ziyan Wu; Shukui Liu (Earthquake Engineering and Engineering Vibration, 2012)

Relationship between triphasic mechanical properties of articular cartilage and osteoarthritic grade - HaiJun Niu; ChengRui Liu; Ang Li; Qing Wang; YueXiang Wang; DeYu Li; YuBo Fan (Science China Life Sciences, 2012)

Isolation of a cinnamoyl CoA reductase gene involved in formation of stone cells in pear (Pyrus pyrifolia) - Xiao-Peng Lu; Yong-Zhong Liu; Ji-Cui An; Hong-Ju Hu; Shu-Ang Peng (Acta Physiologiae Plantarum, 2011)

Genetic structure analysis of natural Sargassum muticum (Fucales, Phaeophyta) populations using RAPD and ISSR markers - Fengjuan Zhao; Fuli Liu; Jidong Liu; Put O. Ang; Delin Duan (Journal of Applied Phycology, 2008)

Measurements of nighttime nitrate radical concentrations in the atmosphere by long-path differential optical absorption spectroscopy - Suwen Li; Wenqing Liu; Pinhua Xie; Ang Li; Min Qin; Ke Dou (Advances in Atmospheric Sciences, 2007)

Phosphine in the Urban Air of Beijing and Its Possible Sources - Liu Ji-ang; Cao Haifeng Zhuang Yahui; Peter Kuschk; Frank Eismann; Dietmar Glindemann (Water, Air, & Soil Pollution, 1999)